A cross-tissue protein profiling atlas reveals distinct cDC2 subpopulations within the murine conventional dendritic cell network - Amon, Lukas; Lehmann, Christian; Seichter, A.; Heger, Lukas; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

A humanized mouse identifies the bone marrow as a niche with low therapeutic IgG activity - Lux, Anja; Seeling, Michaela; Baerenwaldt, Anne; Lehmann, Birgit; Schwab, Inessa; Repp, Roland; Meidenbauer, Norbert; Mackensen, Andreas; Hartmann, Arndt; Heidkamp, Gordon Frederik; Dudziak, Diana; Nimmerjahn, Falk (Cell Reports, 2014)
Genetic differences between humans and in vivo model systems, including mice and nonhuman primates, make it difficult to predict the efficacy of immunoglobulin G (IgG) activity in humans and understand the molecular and cellular mechanisms underlying that activity. To bridge this gap, we established a small-animal model system that allowed us to study human IgG effector functions in the context of an intact human immune system without the interference of murine Fc? receptors expressed on mouse innate immune effector cells in vivo. Using a model of B cell depletion with different human IgG variants that recognize CD20, we show that this humanized mouse model can provide unique insights into the mechanism of human IgG activity in vivo. Importantly, these studies identify the bone marrow as a niche with low therapeutic IgG activity.
EVALuna2:6588

A Modified Surgical Technique for Kidney Transplantation in Mice - Yin, Decheng; Fu, Jian; Chen, Rongjun; Shushakova, Nelli; Allabauer, Ida; Wei, Xinyi; Schiffer, Mario; Dudziak, Diana; Rong, Song; Hörning, André (Journal of Visualized Experiments, 2022)
Kidney transplantation in mice is a complicated and challenging surgery procedure. There are very few publications demonstrating the key steps of this operation. Therefore, this article introduces the technique and points out the surgical caveats associated with this operation. In addition, important modifications in comparison to the conventional procedure are demonstrated. Firstly, a patch of the abdominal aorta is cut and prepared so that the proximal bifurcations of the renal artery, including the ureteral artery are transected together with the donor kidney en bloc. This reduces the risk of a ureter necrosis and avoids the development of a urinary tract occlusion. Secondly, a new method of the vascular anastomosis is demonstrated that allows the operator to flexibly increase or decrease the size of the anastomosis after renal transplant reperfusion has already been initiated. This avoids the development of vessel strictures and intraabdominal bleeding. Thirdly, a technique that enables the anastomosis of the delicate donor ureter and the recipient bladder that does not cause a trauma is shown. Adopting this protocol can shorten the operation time and reduces the damage to the recipient's bladder, thereby significantly increasing the operation success rate for the recipient mice.
CRIS-Team Scopus Importer:2022-08-19

Antigen delivery to CD11c+CD8- dendritic cells induces protective immune responses against experimental melanoma in mice in vivo - Neubert, Kirsten; Lehmann, Christian; Heger, Lukas; Baranska, Anna; Staedtler, Anna Maria; Buchholz, Veit R.; Yamazaki, Sayuri; Heidkamp, Gordon Frederik; Eissing, Nathalie; Zebroski, Henry; Nussenzweig, Michel C.; Nimmerjahn, Falk; et al. (Journal of Immunology, 2014)
Dendritic cells (DCs) are central modulators of immune responses and, therefore, interesting target cells for the induction of antitumor immune responses. Ag delivery to select DC subpopulations via targeting Abs to DC inhibitory receptor 2 (DCIR2, clone 33D1) or to DEC205 was shown to direct Ags specifically to CD11c(+)CD8(-) or CD11c(+)CD8(+) DCs, respectively, in vivo. In contrast to the increasing knowledge about the induction of immune responses by efficiently cross-presenting CD11c(+)CD8(+) DCs, little is known about the functional role of Ag-presenting CD11c(+)CD8(-) DCs with regard to the initiation of protective immune responses. In this study, we demonstrate that Ag targeting to the CD11c(+)CD8(-) DC subpopulation in the presence of stimulating anti-CD40 Ab and TLR3 ligand polyinosinic-polycytidylic acid induces protective responses against rapidly growing tumor cells in naive animals under preventive and therapeutic treatment regimens in vivo. Of note, this immunization protocol induced a mixed Th1/Th2-driven immune response, irrespective of which DC subpopulation initially presented the Ag. Our results provide important information about the role of CD11c(+)CD8(-) DCs, which have been considered to be less efficient at cross-presenting Ags, in the induction of protective antitumor immune responses.
EVALuna2:19490

Antigen targeting of Fc receptors induces strong and functional relevant T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subsets - Lehmann, Christian; Baranska, A.; Heidkamp, Gordon Frederik; Amon, Lukas; Seeling, Michaela; Soulat, D.; Krug, A. B.; Ravetch, J. V.; Leusen, J. H. W.; Nimmerjahn, Falk; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Antigen targeting of Fc receptors induces strong T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subset - Lehmann, Christian; Baranska, A.; Heidkamp, Gordon Frederik; Seeling, Michaela; Soulat, D.; Krug, A.; Ravetch, J.; Leusen, J.; Nimmerjahn, Falk; Dudziak, Diana (2018)
EVALuna2:34795

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subset - Lehmann, C. H. K.; Baranska, A.; Heidkamp, G. F.; Heger, L.; Neubert, K.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, S.; Seeling, M.; Kießling, Melissa; et al. (2017)
EVALuna2:33396

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subsets - Lehmann, Christian; Baranska, A.; Heidkamp, Gordon Frederik; Heger, Lukas; Neubert, K.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, S.; Seeling, Michaela; Kießling, Melissa; et al. (2017)
EVALuna2:33397

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signalling - Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon Frederik; Kiessling, M.; Soulat, Didier; Krug, A.; Ravetch, J. V.; Leusen, J. H.; Nimmerjahn, Falk; Dudziak, Diana (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2016)
Created from Fastlane, WoS look-up

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signalling - Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon Frederik; Kiessling, M.; Soulat, D.; Krug, A.; Ravetch, J. V.; Leusen, J. H.; Nimmerjahn, Falk; Dudziak, Diana (Journal of Investigative Dermatology, 2016)

B cells are critical for autoimmune pathology in Scurfy mice. - Aschermann, Susanne; Lehmann, Christian; Mihai, Sidonia; Schett, Georg; Dudziak, Diana; Nimmerjahn, Falk (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Impaired regulatory T-cell function results in a severe chronic autoimmune disease affecting multiple organs in Scurfy mice and humans with the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. Previous studies have shown that T helper cells but not cytotoxic T cells are critical for the disease pathology. Whether this T-cell subset is responsible directly for tissue inflammation or rather indirectly via the interaction with B cells or myeloid cells is largely unknown. To study this and to identify potential therapeutic targets for this lethal disease we investigated the contribution of B cells to this complex autoimmune phenotype. We show that B cells and the production of autoantibodies plays a major role for skin, liver, lung, and kidney inflammation and therapeutic depletion of B cells resulted in reduced tissue pathology and in prolonged survival. In contrast, the absence of B cells did not impact systemic T-cell activation and hyperreactivity, indicating that autoantibody production by B cells may be a major factor for the autoimmune pathology in mice deficient for regulatory T cells.

BCL2 Inhibition Reveals a Dendritic Cell-Specific Immune Checkpoint That Controls Tumor Immunosurveillance - Zhao, Liwei; Liu, Peng; Mao, Misha; Zhang, Shuai; Bigenwald, Camille; Dutertre, Charles Antoine; Lehmann, Christian; Pan, Hui; Paulhan, Nicolas; Amon, Lukas; Buqué, Aitziber; Yamazaki, Takahiro; et al. (Cancer Discovery, 2023)
We developed a phenotypic screening platform for the functional exploration of dendritic cells (DC). Here, we report a genome-wide CRISPR screen that revealed BCL2 as an endogenous inhibitor of DC function. Knockout of BCL2 enhanced DC antigen presentation and activation as well as the capacity of DCs to control tumors and to synergize with PD-1 blockade. The pharmacologic BCL2 inhibitors venetoclax and navitoclax phenocopied these effects and caused a cDC1-dependent regression of orthotopic lung cancers and fibrosarcomas. Thus, solid tumors failed to respond to BCL2 inhibition in mice constitutively devoid of cDC1, and this was reversed by the infusion of DCs. Moreover, cDC1 depletion reduced the therapeutic efficacy of BCL2 inhibitors alone or in combination with PD-1 blockade and treatment with venetoclax caused cDC1 activation, both in mice and in patients. In conclusion, genetic and pharmacologic BCL2 inhibition unveils a DC-specific immune checkpoint that restrains tumor immunosurveillance. SIGNIFICANCE: BCL2 inhibition improves the capacity of DCs to stimulate anticancer immunity and restrain cancer growth in an immunocompetent context but not in mice lacking cDC1 or mature T cells. This study indicates that BCL2 blockade can be used to sensitize solid cancers to PD-1/PD-L1-targeting immunotherapy. This article is featured in Selected Articles from This Issue, p. 2293.
CRIS-Team Scopus Importer:2023-11-17

Cathepsin S provokes interleukin-6 (IL-6) trans-signaling through cleavage of the IL-6 receptor in vitro - Flynn, Charlotte M.; Garbers, Yvonne; Düsterhöft, Stefan; Wichert, Rielana; Lokau, Juliane; Lehmann, Christian; Dudziak, Diana; Schröder, Bernd; Becker-Pauly, Christoph; Rose-John, Stefan; Aparicio-Siegmund, Samadhi; Garbers, Christoph (Scientific Reports, 2020)
The cytokine interleukin-6 (IL-6) fulfills its pleiotropic functions via different modes of signaling. Regenerative and anti-inflammatory activities are mediated via classic signaling, in which IL-6 binds to the membrane-bound IL-6 receptor (IL-6R). For IL-6 trans-signaling, which accounts for the pro-inflammatory properties of the cytokine, IL-6 activates its target cells via soluble forms of the IL-6R (sIL-6R). We have previously shown that the majority of sIL-6R in human serum originates from proteolytic cleavage and mapped the cleavage site of the IL-6R. The cleavage occurs between Pro-355 and Val-356, which is the same cleavage site that the metalloprotease ADAM17 uses in vitro. However, sIL-6R serum levels are unchanged in hypomorphic ADAM17ex/ex mice, making the involvement of ADAM17 questionable. In order to identify other proteases that could be relevant for sIL-6R generation in vivo, we perform a screening approach based on the known cleavage site. We identify several candidate proteases and characterize the cysteine protease cathepsin S (CTSS) in detail. We show that CTSS is able to cleave the IL-6R in vitro and that the released sIL-6R is biologically active and can induce IL-6 trans-signaling. However, CTSS does not use the Pro-355/Val-356 cleavage site, and sIL-6R serum levels are not altered in Ctss−/− mice. In conclusion, we identify a novel protease of the IL-6R that can induce IL-6 trans-signaling, but does not contribute to steady-state sIL-6R serum levels.
CRIS-Team Scopus Importer:2020-12-25

Cdc42-dependent actin dynamics controls maturation and secretory activity of dendritic cells - Schulz, Anna M.; Stutte, Susanne; Hogl, Sebastian; Luckashenak, Nancy; Dudziak, Diana; Leroy, Celine; Forne, Ignasi; Imhof, Axel; Mueller, Stephan A.; Brakebusch, Cord H.; Lichtenthaler, Stefan F.; Brocker, Thomas (The Journal of Cell Biology, 2015)
Cell division cycle 42 (Cdc42) is a member of the Rho guanosine triphosphatase family and has pivotal functions in actin organization, cell migration, and proliferation. To further study the molecular mechanisms of dendritic cell (DC) regulation by Cdc42, we used Cdc42-deficient DCs. Cdc42 deficiency renders DCs phenotypically mature as they up-regulate the co-stimulatory molecule CD86 from intracellular storages to the cell surface. Cdc42 knockout DCs also accumulate high amounts of invariant chain-major histocompatibility complex (MHC) class II complexes at the cell surface, which cannot efficiently present peptide antigens (Ag's) for priming of Ag-specific CD4 T cells. Proteome analyses showed a significant reduction in lysosomal MHC class II-processing proteins, such as cathepsins, which are lost from DCs by enhanced secretion. As these effects on DCs can be mimicked by chemical actin disruption, our results propose that Cdc42 control of actin dynamics keeps DCs in an immature state, and cessation of Cdc42 activity during DC maturation facilitates secretion as well as rapid up-regulation of intracellular molecules to the cell surface.
EVALuna2:19559

Characterization and Manipulation of the Crosstalk Between Dendritic and Natural Killer Cells Within the Tumor Microenvironment - Jacobs, Benedikt; Gebel, Veronika; Heger, Lukas; Greze, Victoria; Schild, Hansjorg; Dudziak, Diana; Ullrich, Evelyn (Frontiers in Immunology, 2021)
Cellular therapy has entered the daily clinical life with the approval of CAR T cell therapeutics and dendritic cell (DCs) vaccines in the US and the EU. In addition, numerous other adoptive cellular products, including natural killer (NK) cells, are currently evaluated in early phase I/ II clinical trials for the treatment of cancer patients. Despite these promising accomplishments, various challenges remain to be mastered in order to ensure sustained therapeutic success. These include the identification of strategies by which tumor cells escape the immune system or establish an immunosuppressive tumor microenvironment (TME). As part of the innate immune system, DCs and NK cells are both present within the TME of various tumor entities. While NK cells are well known for their intrinsic anti-tumor activity by their cytotoxicity capacities and the secretion of pro-inflammatory cytokines, the role of DCs within the TME is a double-edged sword as different DC subsets have been described with either tumor-promoting or -inhibiting characteristics. In this review, we will discuss recent findings on the interaction of DCs and NK cells under physiological conditions and within the TME. One focus is the crosstalk of various DC subsets with NK cells and their impact on the progression or inhibition of tumor growth. In addition, we will provide suggestions to overcome the immunosuppressive outcome of the interaction of DCs and NK cells within the TME.
CRIS-Team Scopus Importer:2021-06-11
Keywords: cellular therapies; DC-NK cell interaction; dendritic cells; NK cells; tumor microenvironment

Chemotherapy-induced ileal crypt apoptosis and the ileal microbiome shape immunosurveillance and prognosis of proximal colon cancer - Roberti, Maria Paula; Yonekura, Satoru; Duong, Connie P.M.; Picard, Marion; Ferrere, Gladys; Tidjani Alou, Maryam; Rauber, Conrad; Iebba, Valerio; Lehmann, Christian; Amon, Lukas; Dudziak, Diana; Derosa, Lisa; et al. (Nature Medicine, 2020)
The prognosis of colon cancer (CC) is dictated by tumor-infiltrating lymphocytes, including follicular helper T (TFH) cells and the efficacy of chemotherapy-induced immune responses. It remains unclear whether gut microbes contribute to the elicitation of TFH cell-driven responses. Here, we show that the ileal microbiota dictates tolerogenic versus immunogenic cell death of ileal intestinal epithelial cells (IECs) and the accumulation of TFH cells in patients with CC and mice. Suppression of IEC apoptosis led to compromised chemotherapy-induced immunosurveillance against CC in mice. Protective immune responses against CC were associated with residence of Bacteroides fragilis and Erysipelotrichaceae in the ileum. In the presence of these commensals, apoptotic ileal IECs elicited PD-1+ TFH cells in an interleukin-1R1- and interleukin-12-dependent manner. The ileal microbiome governed the efficacy of chemotherapy and PD-1 blockade in CC independently of microsatellite instability. These findings demonstrate that immunogenic ileal apoptosis contributes to the prognosis of chemotherapy-treated CC.
CRIS-Team Scopus Importer:2020-06-02

Circumventing pyroptosis via hyperactivation shapes superior immune responses of human type 2 dendritic cells compared to type 3 dendritic cells - Hatscher, Lukas; Kaszubowski, Tomasz; Amon, Lukas; Dudziak, Diana; Heger, Lukas (European Journal of Immunology, 2023)
Exploiting inflammasome activation in dendritic cells (DCs) is a promising approach to fight cancer and to augment adjuvant-induced immune responses. As inflammasome formation is typically accompanied by pyroptosis, hyperactivation—defined as inflammasome activation in the absence of pyroptosis—represents a mechanism of circumventing cell death of DCs while simultaneously benefitting from inflammasome signaling. We previously demonstrated a unique specialization for inflammasome responses and hyperactivation of human cDC2 among all human DC subsets. As recent investigations revealed heterogeneity among the human cDC2 population, we aimed to analyze whether the two recently identified cDC2 subpopulations DC2 and DC3 harbor similar or different inflammasome characteristics. Here, we report that both DC2 and DC3 are inflammasome competent. We show that DC3 generally induce stronger inflammasome responses, which are associated with higher levels of cell death. Although DC2 release lower levels of inflammasome-dependent IL-1β, they induce stronger CD4+ T cell responses than DC3, which are predominantly skewed toward a TH1/TH17 phenotype. Thus, mainly DC2 seem to be able to enter a state of hyperactivation, resulting in enhanced T cell stimulatory capacity.
CRIS-Team Scopus Importer:2023-03-31
Keywords: DC2; DC3; dendritic cells; inflammasome; pyroptosis

Citrate-coated superparamagnetic iron oxide nanoparticles enable a stable non-spilling loading of t cells and their magnetic accumulation - Boosz, Philipp; Pfister, Felix; Stein, René; Friedrich, Bernhard; Fester, Lars; Band, Julia; Mühlberger, Marina; Schreiber, Eveline; Lyer, Stefan; Dudziak, Diana; Alexiou, Christoph; Janko, Christina (Cancers, 2021)
T cell infiltration into a tumor is associated with a good clinical prognosis of the patient and adoptive T cell therapy can increase anti-tumor immune responses. However, immune cells are often excluded from tumor infiltration and can lack activation due to the immune-suppressive tumor microenvironment. To make T cells controllable by external forces, we loaded primary human CD3+ T cells with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONs). Since the efficacy of magnetic targeting depends on the amount of SPION loading, we investigated how experimental conditions influence nanoparticle uptake and viability of cells. We found that loading in the presence of serum improved both the colloidal stability of SPIONs and viability of T cells, whereas stimulation with CD3/CD28/CD2 and IL-2 did not influence nanoparticle uptake. Further-more, SPION loading did not impair cytokine secretion after polyclonal stimulation. We finally achieved 1.4 pg iron loading per cell, which was both located intracellularly in vesicles and bound to the plasma membrane. Importantly, nanoparticles did not spill over to non-loaded cells. Since SPION-loading enabled efficient magnetic accumulation of T cells in vitro under dynamic condi-tions, we conclude that this might be a good starting point for the investigation of in vivo delivery of immune cells.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Adoptive T cell transfer; Immune therapy; Magnetic targeting; Nanomedicine; Solid tumor; Superparamagnetic iron oxide nanoparticles (SPIONs); Targeted transport

CLEC10A Is a Specific Marker for Human CD1c+ Dendritic Cells and Enhances Their Toll-Like Receptor 7/8-Induced Cytokine Secretion - Heger, Lukas; Balk, Silke; Lühr, Jennifer; Heidkamp, Gordon Frederik; Lehmann, Christian; Hatscher, Lukas; Purbojo, Ariawan; Hartmann, Arndt; Garcia-Martin, Fayna; Nishimura, Shin-Ichiro; Cesnjevar, Robert; Nimmerjahn, Falk; et al. (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are major players for the induction of immune responses. Apart from plasmacytoid DCs (pDCs), human DCs can be categorized into two types of conventional DCs: CD141+ DCs (cDC1) and CD1c+ DCs (cDC2). Defining uniquely expressed surface markers on human immune cells is not only important for the identification of DC subpopulations but also a prerequisite for harnessing the DC subset-specific potential in immunomodulatory approaches, such as antibody-mediated antigen targeting. Although others identified CLEC9A as a specific endocytic receptor for CD141+ DCs, such a receptor for CD1c+ DCs has not been discovered, yet. By performing transcriptomic and flow cytometric analyses on human DC subpopulations from different lymphohematopoietic tissues, we identified CLEC10A (CD301, macrophage galactose-type C-type lectin) as a specific marker for human CD1c+ DCs. We further demonstrate that CLEC10A rapidly internalizes into human CD1c+ DCs upon binding of a monoclonal antibody directed against CLEC10A. The binding of a CLEC10A-specific bivalent ligand (the MUC-1 peptide glycosylated with N-acetylgalactosamine) is limited to CD1c+ DCs and enhances the cytokine secretion (namely TNFα, IL-8, and IL-10) induced by TLR 7/8 stimulation. Thus, CLEC10A represents not only a candidate to better define CD1c+ DCs-due to its high endocytic potential-CLEC10A also exhibits an interesting candidate receptor for future antigen-targeting approaches.
EVALuna2:34257

Clec12A, CD301b, and FcγRIIB/III define the heterogeneity of murine DC2s and DC3s - Amon, Lukas; Seichter, Anna; Vurnek, Damir; Heger, Lukas; Lächele, Lukas; Tochoedo, Nounagnon Romaric; Kaszubowski, Tomasz; Hatscher, Lukas; Baranska, Anna; Tchitashvili, Giorgi; Nimmerjahn, Falk; Lehmann, Christian; et al. (Cell Reports, 2024)
Over the last decade, multiple studies have investigated the heterogeneity of murine conventional dendritic cells type 2 (cDC2s). However, their phenotypic similarity with monocytes and macrophages renders their clear identification challenging. By creating a protein atlas utilizing multiparameter flow cytometry, we show that ESAM+ cDC2s are a specialized feature of the spleen strongly differing in their proteome from other cDC2s. In contrast, all other tissues are populated by Clec12A+ cDC2s or Clec12A− cDC2s (high or low for Fcγ receptors, C-type lectin receptors, and CD11b, respectively), rendering Clec12A+ cDC2s classical sentinels. Further, expression analysis of CD301b, Clec12A, and FcγRIIB/III provides a conserved definition of cDC2 heterogeneity, including the discovery of putative FcγRIIB/III+ DC3s across tissues. Finally, our data reveal that cell identity (ontogeny) dictates the proteome that is further fine-tuned by the tissue environment on macrophages and dendritic cells (DCs), while monocytes and plasmacytoid DCs (pDCs) display subset intrinsic default settings.
CRIS-Team Scopus Importer:2024-04-12
Keywords: CD301b; CP: Immunology; DC3; dendritic cells; heterogeneity; macrophages; monocytes; mouse; myeloid cells; proteome atlas; subpopulations

Combination therapies to improve DC-based treatment of melanoma - Seretis, A.; Cappellano, G.; Bellmann, L.; Schachtl-Riess, J.; Steindl, R.; Prokopi, N.; Ortner-Tobider, D.; Komenda, K.; Tripp, C.; Brinckerhoff, C. E.; Lühr, Jennifer; Amon, Lukas; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-11

Comparative analysis of human dendritic cell subpopulations in steady state and inflammation - Heger, Lukas; Heidkamp, Gordon Frederik; Lehmann, Christian; Eissing, N.; Söder, Stephan; Hartmann, Arndt; Zenk, J.; Alexiou, Christoph; Schuler, Gerold; Purbojo, Ariawan; Cesnjevar, Robert; Nimmerjahn, Falk; et al. (2017)
EVALuna2:33136

Comparative analysis of human dendritic cell subpopulations in steady state and inflammation - Heger, Lukas; Heidkamp, Gordon Frederik; Lehmann, Christian; Söder, Stephan; Hartmann, Arndt; Alexiou, Christoph; Schuler, Gerold; Purbojo, Ariawan; Cesnjevar, Robert; Nimmerjahn, Falk; Dudziak, Diana (2018)
EVALuna2:34382

CXCR4 blockade reduces the severity of murine heart allograft rejection by plasmacytoid dendritic cell-mediated immune regulation - Fu, Jian; Lehmann, Christian; Wang, Xinning; Wahlbuhl, Mandy; Allabauer, Ida; Wilde, Benjamin; Amon, Lukas; Dolff, Sebastian; Cesnjevar, Robert; Kribben, Andreas; Wölfle, Joachim; Rascher, Wolfgang; et al. (Scientific Reports, 2021)
Allograft-specific regulatory T cells (Treg cells) are crucial for long-term graft acceptance after transplantation. Although adoptive Treg cell transfer has been proposed, major challenges include graft-specificity and stability. Thus, there is an unmet need for the direct induction of graft-specific Treg cells. We hypothesized a synergism of the immunotolerogenic effects of rapamycin (mTOR inhibition) and plerixafor (CXCR4 antagonist) for Treg cell induction. Thus, we performed fully-mismatched heart transplantations and found combination treatment to result in prolonged allograft survival. Moreover, fibrosis and myocyte lesions were reduced. Although less CD3+ T cell infiltrated, higher Treg cell numbers were observed. Noteworthy, this was accompanied by a plerixafor-dependent plasmacytoid dendritic cells-(pDCs)-mobilization. Furthermore, in vivo pDC-depletion abrogated the plerixafor-mediated Treg cell number increase and reduced allograft survival. Our pharmacological approach allowed to increase Treg cell numbers due to pDC-mediated immune regulation. Therefore pDCs can be an attractive immunotherapeutic target in addition to plerixafor treatment.
CRIS-Team Scopus Importer:2021-12-24

CXCR4-SDF1 alpha Blockade Reduces the Severity of Murine Heart Allograft Rejection - Fu, J.; Wahlbuhl, Mandy; Wang, X.; Wilde, B.; Jing, L.; Kribben, A.; Hoyer, P.; Lehmann, C. H. K.; Dudziak, Diana; Witzke, O.; Hoerning, A. (2017)
EVALuna2:34369

DC subset–specific induction of T cell responses upon antigen uptake via Fcγ receptors in vivo - Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon Frederik; Heger, Lukas; Neubert, Kirsten; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, Simone; Seeling, Michaela; Kießling, Melissa; et al. (Journal of Experimental Medicine, 2017)
Dendritic cells (DCs) are efficient antigen-presenting cells equipped with various cell surface receptors for the direct or indirect recognition of pathogenic microorganisms. Interestingly, not much is known about the specific expression pattern and function of the individual activating and inhibitory Fcγ receptors (FcγRs) on splenic DC subsets in vivo and how they contribute to the initiation of T cell responses. By targeting antigens to select activating and the inhibitory FcγR in vivo, we show that antigen uptake under steady-state conditions results in a short-term expansion of antigen-specific T cells, whereas under inflammatory conditions especially, the activating FcγRIV is able to induce superior CD4+ and CD8+ T cell responses. Of note, this effect was independent of FcγR intrinsic activating signaling pathways. Moreover, despite the expression of FcγRIV on both conventional splenic DC subsets, the induction of CD8+ T cell responses was largely dependent on CD11c+CD8+ DCs, whereas CD11c+CD8− DCs were critical for priming CD4+ T cell responses.<br
Keywords: Infectious disease and host defense; Innate immunity and inflammation; Tolerance

Deficiency of the Intramembrane Protease SPPL2a Alters Antimycobacterial Cytokine Responses of Dendritic Cells - Gradtke, Ann-Christine; Mentrup, Torben; Lehmann, Christian; Cabrera-Cabrera, Florencia; Desel, Christine; Okakpu, Darian; Assmann, Maike; Dalpke, Alexander; Schaible, Ulrich E.; Dudziak, Diana; Schroder, Bernd (Journal of Immunology, 2021)
Signal peptide peptidase-like 2a (SPPL2a) is an aspartyl intramembrane protease essential for degradation of the invariant chain CD74. In humans, absence of SPPL2a leads to Mendelian susceptibility to mycobacterial disease, which is attributed to a loss of the dendritic cell (DC) subset conventional DC2. In this study, we confirm depletion of conventional DC2 in lymphatic tissues of SPPL2a(-/-) mice and demonstrate dependence on CD74 using SPPL2a(-/-) CD74(-1-) mice. Upon contact with mycobacteria, SPPL2a(-/-) bone marrow-derived DCs show enhanced secretion of IL-1 beta, whereas production of IL-10 and IFN-beta is reduced. These effects correlated with modulated responses upon selective stimulation of the pattern recognition receptors TLR4 and Dectin-1. In SPPL2a(-/-) bone marrow-derived DCs, Dectin-1 is redistributed to endosomal compartments. Thus, SPPL2a deficiency alters pattern recognition receptor pathways in a CD74-dependent way, shifting the balance from anti- to proinflammatory cytokines in antimycobacterial responses. We propose that in addition to the DC reduction, this altered DC functionality contributes to Mendelian susceptibility to mycobacterial disease upon SPPL2a deficiency.
CRIS-Team WoS Importer:2021-01-15

Dendritic cells are involved in the resolution of inflammation by IVIg in arthritis - Lehmann, Christian; Amon, Lukas; Seichter, A.; Brückner, Christin; Altmann, Leon; Heger, Lukas; Heger, L.; Ravetch, J. V.; Nimmerjahn, Falk; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Dendritic Cells Control Regulatory T Cell Function Required for Maintenance of Intestinal Tissue Homeostasis - Hilpert, Cornelia; Sitte, Selina; Arnold, Harald; Lehmann, Christian; Dudziak, Diana; Mattner, Jochen; Vöhringer, David (Journal of Immunology, 2019)
Dendritic cells (DCs) together with regulatory T cells (Tregs) are essential mediators of immune homeostasis. Disruption of function or frequency of either cell type can lead to fatal autoimmunity. We previously described that mice constitutively lacking DCs (∆DC) develop autoimmunity characterized by reduced body weight, autoantibodies, and pronounced intestinal inflammation. In this study, we show that lack of DCs leads to an altered gene expression profile in peripheral but not thymic Tregs with increased expression of inhibitory receptors. The suppressive function of Tregs from ΔDC mice was impaired in T cell cocultures. In a model of transfer colitis, Tregs from ∆DC mice were only functional in the presence of DCs in recipient mice. Lack of MHC class II on DCs also resulted in upregulation of inhibitory receptors on Tregs, reduced body weight, and elevated serum IgA levels. Further analysis of the IgA response revealed an expansion of IgA+ germinal center B cells and plasma cells in mesenteric lymph nodes and more IgA-coated commensal bacteria in feces of ∆DC mice. Thus, we show a critical role for DCs to establish intestinal homeostasis by regulating Treg function for prevention of spontaneous inflammation.
CRIS-Team Scopus Importer:2019-11-29

Development of combination therapy to delay resistance in BRAF-inhibitor treated melanoma - Seretis, A.; Cappellano, G.; Bellmann, L.; Hornsteiner, F.; Tripp, C. H.; Ortner-Tobider, D.; Mullins, D. W.; Amon, Lukas; Lehmann, Christian; Dudziak, Diana; Stoitzner, P. (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

Direct delivery of antigens to dendritic cells via antibodies specific for endocytic receptors as a promising strategy for future therapies - Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Dudziak, Diana (Vaccines, 2016)
Dendritic cells (DCs) are the most potent professional antigen presenting cells and are therefore indispensable for the control of immunity. The technique of antibody mediated antigen targeting to DC subsets has been the basis of intense research for more than a decade. Many murine studies have utilized this approach of antigen delivery to various kinds of endocytic receptors of DCs both in vitro and in vivo. Today, it is widely accepted that different DC subsets are important for the induction of select immune responses. Nevertheless, many questions still remain to be answered, such as the actual influence of the targeted receptor on the initiation of the immune response to the delivered antigen. Further efforts to better understand the induction of antigen-specific immune responses will support the transfer of this knowledge into novel treatment strategies for human diseases. In this review, we will discuss the state-of-the-art aspects of the basic principles of antibody mediated antigen targeting approaches. A table will also provide a broad overview of the latest studies using antigen targeting including addressed DC subset, targeted receptors, outcome, and applied coupling techniques.
Created from Fastlane, Scopus look-up
Keywords: Antigen targeting; Antigen targeting antibodies; Cancer; CLR; DC; DCIR; DEC205; Dendritic cell subsets; moDC; Vaccine

Dynamic regulation and differential compartmentaliztion of C-type lectin receptors in the dendritic cell membrane - Lühr, Jennifer; Eissing, N.; Heger, Lukas; Lehmann, C.; Heidkamp, Gordon Frederik; Nimmerjahn, Falk; Balint, S.; Sezgin, E.; Eggeling, C.; Dustin, M.; Dudziak, Diana (2018)
EVALuna2:34794

Easy performance of 6-color confocal immunofluorescence with 4-laser line microscopes - Eissing, Nathalie; Heger, Lukas; Baranska, Anna; Cesnjevar, Robert; Büttner, Maike; Söder, Stephan; Hartmann, Arndt; Heidkamp, Gordon Frederik; Dudziak, Diana (Immunology Letters, 2014)
Confocal laser scanning microscopy is an advanced technique for imaging tissue samples in vitro and in vivo at high optical resolution. The development of new fluorochrome variants do not only make it possible to perform multicolor flow cytometry of single cells, but in combination with high resolution laser scanning systems also to investigate the distribution of cells in lymphoid tissues by confocal immunofluorescence analyses, thus allowing the distinction of various cell populations directly in the tissue. Here, we provide a protocol for the visualization of at least six differently fluorochrome-labeled antibodies at the same time using a conventional confocal laser scanning microscope with four laser lines (405 nm, 488 nm, 555 nm, and 639 nm laser wavelength) in both murine and human tissue samples. We further demonstrate that compensation correction algorithms are not necessary to reduce spillover of fluorochromes into other channels when the used fluorochromes are combined according to their specific emission bands and the varying Stokes shift for co-excited fluorochromes with the same laser line.
EVALuna2:6626

Editorial: Multiomics and multiparametric analyses to characterize myeloid cell subsets - Vu Manh, Thien Phong; Dalod, Marc; Dudziak, Diana (Frontiers in Immunology, 2023)
CRIS-Team Scopus Importer:2023-10-20
Keywords: cell state characterization; cell type identification; multiomics; multiparametric analysis; myeloid cells

Editorial: Sentinel CLECs at Immunological Decision Nodes - Hoober, J. Kenneth; van Vliet, Sandra J.; Dudziak, Diana; Eggink, Laura L. (Frontiers in Immunology, 2020)
CRIS-Team Scopus Importer:2020-10-02
Keywords: CLEC receptors; dendritic cells; immunomodulation; ligand diversity; sentinel receptors

Efficient generation of a monoclonal antibody against the human C-type lectin receptor DCIR by targeting murine dendritic cells. - Heidkamp, Gordon Frederik; Neubert, Kirsten; Härtel, Eric; Nimmerjahn, Falk; Nussenzweig, Michel C.; Dudziak, Diana (Immunology letters, 2010)
Dendritic cells (DCs) are very important for the generation of long lasting immune responses against pathogens or the induction of anti-tumor responses. Targeting antigen to dendritic cells via monoclonal antibodies specific for DC cell surface receptors such as DEC205 was shown to elicit potent cellular and humoral immune responses in vivo. Therefore, we investigated whether this novel strategy might also be useful for the generation of new monoclonal antibodies against molecules of choice. We show, that by targeting the extracellular domain of the human C-type lectin receptor ClecSF6/DCIR/LLIR (hDCIR) to DEC205 on DCs in vivo, we were able to generate highly specific monoclonal antibodies against hDCI

Engulfment of mast cell secretory granules on skin inflammation boosts dendritic cell migration and priming efficiency - Dudeck, Jan; Froebel, Julia; Kotrba, Johanna; Lehmann, Christian; Dudziak, Diana; Speier, Stephan; Nedospasov, Sergei A.; Schraven, Burkhart; Dudeck, Anne (Journal of Allergy and Clinical Immunology, 2019)
Background: Mast cells (MCs)are best known as key effector cells of allergic reactions, but they also play an important role in host defense against pathogens. Despite increasing evidence for a critical effect of MCs on adaptive immunity, the underlying mechanisms are poorly understood. Objective: Here we monitored MC intercellular communication with dendritic cells (DCs), MC activation, and degranulation and tracked the fate of exocytosed mast cell granules (MCGs)during skin inflammation. Methods: Using a strategy to stain intracellular MCGs in vivo, we tracked the MCG fate after skin inflammation–induced MC degranulation. Furthermore, exogenous MCGs were applied to MC-deficient mice by means of intradermal injection. MCG effects on DC functionality and adaptive immune responses in vivo were assessed by combining intravital multiphoton microscopy with flow cytometry and functional assays. Results: We demonstrate that dermal DCs engulf the intact granules exocytosed by MCs on skin inflammation. Subsequently, the engulfed MCGs are actively shuttled to skin-draining lymph nodes and finally degraded inside DCs within the lymphoid tissue. Most importantly, MCG uptake promotes DC maturation and migration to skin-draining lymph nodes, partially through MC-derived TNF, and boosts their T-cell priming efficiency. Surprisingly, exogenous MCGs alone are sufficient to induce a prominent DC activation and T-cell response. Conclusion: Our study highlights a unique feature of peripheral MCs to affect lymphoid tissue–borne adaptive immunity over distance by modifying DC functionality through delivery of granule-stored mediators.
CRIS-Team Scopus Importer:2019-05-03
Keywords: adaptive immune response; dendritic cells; Mast cells; skin inflammation; T-cell response

Environmental signals rather than layered ontogeny imprint the function of type 2 conventional dendritic cells in young and adult mice - Papaioannou, Nikos E.; Salei, Natallia; Rambichler, Stephan; Ravi, Kaushikk; Popovic, Jelena; Küntzel, Vanessa; Lehmann, Christian; Fiancette, Remi; Salvermoser, Johanna; Gajdasik, Dominika W.; Mettler, Ramona; Messerer, Denise; et al. (Nature Communications, 2021)
Conventional dendritic cells (cDC) are key activators of naive T cells, and can be targeted in adults to induce adaptive immunity, but in early life are considered under-developed or functionally immature. Here we show that, in early life, when the immune system develops, cDC2 exhibit a dual hematopoietic origin and, like other myeloid and lymphoid cells, develop in waves. Developmentally distinct cDC2 in early life, despite being distinguishable by fate mapping, are transcriptionally and functionally similar. cDC2 in early and adult life, however, are exposed to distinct cytokine environments that shape their transcriptional profile and alter their ability to sense pathogens, secrete cytokines and polarize T cells. We further show that cDC2 in early life, despite being distinct from cDC2 in adult life, are functionally competent and can induce T cell responses. Our results thus highlight the potential of harnessing cDC2 for boosting immunity in early life.
CRIS-Team Scopus Importer:2021-01-29

Fcγ receptor IIB (FcγRIIB) maintains humoral tolerance in the human immune system in vivo. - Bärenwaldt, Anne; Lux, Anja; Danzer, Heike; Spriewald, Bernd M.; Ullrich, Evelyn; Heidkamp, Gordon Frederik; Dudziak, Diana; Nimmerjahn, Falk (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Maintenance of immunological tolerance is crucial to prevent development of autoimmune disease. The production of autoantibodies is a hallmark of many autoimmune diseases and studies in mouse model systems suggest that inhibitory signaling molecules may be important checkpoints of humoral tolerance. By generating humanized mice with normal and functionally impaired Fcγ receptor IIB (FcγRIIB) variants, we show that the inhibitory Fcγ-receptor is a checkpoint of humoral tolerance in the human immune system in vivo. Impaired human FcγRIIB function resulted in the generation of higher levels of serum immunoglobulins, the production of different autoantibody specificities, and a higher proportion of human plasmablasts and plasma cells in vivo. Our results suggest that the inhibitory FcγRIIB may be an important checkpoint of humoral tolerance in the human immune system.

FcγRIV deletion reveals its central role for IgG2a and IgG2b activity in vivo. - Nimmerjahn, Falk; Lux, Anja; Albert, Heike; Woigk, Melissa; Lehmann, Christian; Dudziak, Diana; Smith, Patrick; Ravetch, J. V. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Cellular Fcγ receptors are essential for IgG-dependent effector functions in vivo. There is convincing evidence that selective activating Fcγ receptors are responsible for the activity of individual IgG subclasses. Thus, IgG1 activity is absent in FcγRIII-deficient mice, and several studies suggest that the activity of the most potent IgG subclasses, IgG2a and IgG2b, might be dependent on either individual or a combination of activating FcγRs. To study the role of individual activating FcγRs for IgG subclass activity, we generated an FcγRIV-deficient mouse and showed that a variety of IgG2a- and IgG2b-dependent effector functions are impaired in the absence of this activating Fc receptor in models of autoimmunity and antibody-dependent cellular cytotoxicity.

Functionalization of T lymphocytes for magnetically controlled immune therapy: Selection of suitable superparamagnetic iron oxide nanoparticles - Mühlberger, Marina; Janko, Christina; Unterweger, Harald; Schreiber, Eveline; Band, Julia; Lehmann, Christian; Dudziak, Diana; Lee, Geoffrey; Alexiou, Christoph; Tietze, Rainer (Journal of Magnetism and Magnetic Materials, 2019)
According to the World Health Organization, cancer is the second most important cause of death in Europe. Due to its manifold manifestations, it is not possible to treat all patients according to a uniform scheme. However, all solid tumors have one thing in common: independent of the tumor's molecular subgroup and the treatment protocol, the immune status of the tumor, especially the amount of tumor infiltrating lymphocytes (TILs), is important for the patient's clinical outcome - the higher the number of TILs, the better the outcome. For this reason it seems desirable to increase the number of TILs. One way to accumulate T cells in the tumor area is to make them magnetizable and attract them with an external magnetic field. Magnetization can be achieved by superparamagnetic iron oxide nanoparticles (SPIONs) which can be bound to the cells' surface or internalized into the cells. For this study, SPIONs with different coatings were synthesized and incubated with immortalized mouse T lymphocytes. SPIONs only stabilized with lauric acid (LA) coated in situ or afterwards showed high toxicity. Addition of an albumin layer increased the biocompatibility but reduced cellular uptake. To increase the cellular uptake the albumin coated particles were aminated, leading to both higher uptake and toxicity, dependent on the degree of amination. In the presence of an externally applied magnetic field, T cells loaded with selected types and amounts of SPIONs were guidable. With this promising pilot study we already can demonstrate that it is possible to attract SPION bearing T cells by an external magnet. To sum up, biocompatibility and uptake of SPIONs by T cells are opposing events. Thus, for the functionalization of T cells with SPIONs the balance between uptake and toxicity must be evaluated carefully.
EVALuna2:35445

Functionalization Of T Lymphocytes With Citrate-Coated Superparamagnetic Iron Oxide Nanoparticles For Magnetically Controlled Immune Therapy - Mühlberger, Marina; Janko, Christina; Unterweger, Harald; Friedrich, Ralf P.; Friedrich, Bernhard; Band, Julia; Cebulla, Nadine; Alexiou, Christoph; Dudziak, Diana; Lee, Geoffrey; Tietze, Rainer (International Journal of Nanomedicine, 2019)
Purpose: Immune activation with T cell tumor infiltration is beneficial for the prognosis of patients suffering from solid cancer. Depending on their immune status, solid tumors can be immunologically classified into three groups: "hot" tumors are infiltrated with T lymphocytes, "cold" tumors are not infiltrated and "immune excluded" tumors are only infiltrated in the peripheral tumor tissue. Checkpoint inhibitors provide new therapeutic options for "hot" tumors by triggering the immune response of T cells. In order to enable this for cold tumors as well, T cells must be enriched in the tumor. Therefore, we use the principle of magnetic targeting to guide T cells loaded with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONCitrate) to the tumor by an externally applied magnetic field. Methods: SPIONCitrate were produced by alkaline coprecipitation of iron(II) and iron(III) chloride and in situ coating with sodium citrate. The concentration-dependent cytocompatibility of the particles was determined by flow cytometry and blood stability assays. Atomic emission spectroscopy was used for the quantification of the particle uptake into T lymphocytes. The attractability of the loaded cells was observed by live-cell imaging in the presence of an externally applied magnetic field. Results: SPIONCitrate displayed good cytocompatibility to T cells and did not show any sign of aggregation in blood. Finally, SPIONCitrate-loaded T cells were strongly attracted by a small external magnet. Conclusion: T cells can be "magnetized" by incorporation of SPIONCitrate for magnetic targeting. The production of the particle-cell hybrid system is straightforward, as the loading process only requires basic laboratory devices and the loading efficiency is sufficient for cells being magnetically controllable. For these reasons, SPIONCitrate are potential suitable candidates for magnetic T cell targeting.
EVALuna2:209938

Functional Specialization of Dendritic Cell Subsets - Heger, Lukas; Amon, Lukas; Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon; Dudziak, Diana (Elsevier, 2022)
Dendritic cells (DCs) are sentinels of the immune system. Under inflammatory conditions, DCs undergo various phenotypical changes, including DC migration, upregulation of co-stimulatory and activating molecules, secretion of cytokines, but also the processing of the engulfed antigens. The DC presents short antigenic peptides on the DC surface as peptide MHC class I or MHC class II complexes to CD8+ or CD4+ T cells, respectively. This article will provide a detailed overview on the antigen processing machineries and specialized functions of the increasing variety of DC subsets in mice and men.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Antigen presentation; Antigen processing; Antigen targeting; Autophagy; CLR; Cross-presentation; DC; Dendritic cell subsets; FcR; Immune responses; MHC-I; MHC-II; PDC; TLR

Functional Specialization of Dendritic Cell Subsets - Heidkamp, Gordon Frederik; Lehmann, Christian; Heger, Lukas; Baransk, A.; Hoffmann, A.; Lühr, Jennifer; Dudziak, Diana (Functional Cell Biology, 2016)
Dendritic cells (DCs) are sentinels of the immune system. Under inflammatory conditions DCs undergo various phenotypical changes, including DC migration, upregulation of co-stimulatory and activating molecules, secretion of cytokines, but also the processing of the engulfed antigens. The DC presents short antigenic peptides on the DC surface as peptide MHC class I or MHC class II complexes to CD8+ or CD4+ T cells, respectively. This article will provide a detailed overview on the antigen processing machineries and specialized functions of the increasing variety of DC subsets in mice and men.
Created from Fastlane, Scopus look-up
Keywords: Antigen presentation; Antigen processing; Antigen targeting; Autophagy; CLR; Cross-presentation; DC; Dendritic cell subsets; FcR; Immune responses; MHC-I; MHC-II; PDC; TLR

Guidelines for DC preparation and flow cytometric analysis of human lymphohematopoietic tissues - Heger, Lukas; Dudziak, Diana; Amon, Lukas; Hatscher, Lukas; Kaszubowski, Tomasz; Lehmann, Christian (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. Within this article, detailed protocols are presented that allow for the generation of single cell suspensions from human lymphohematopoietic tissues including blood, spleen, thymus, and tonsils with a focus on the subsequent analysis of DC via flow cytometry, as well as flow cytometric cell sorting of primary human DC. Further, prepared single cell suspensions as well as cell sorter-purified DC can be subjected to other applications including cellular enrichment procedures, RNA sequencing, functional assays, and many more. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.
CRIS-Team WoS Importer:2023-01-13

Guidelines for DC preparation and flow cytometry analysis of mouse lymphohematopoietic tissues - Amon, Lukas; Dudziak, Diana; Backer, Ronald A. A.; Clausen, Bjoern E.; Gmeiner, Christina; Heger, Lukas; Jacobi, Lukas; Lehmann, Christian; Probst, Hans-Christian; Seichter, Anna; Tchitashvili, Giorgi; Tochoedo, Nounagnon Romaric; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human DC from lymphoid organs, and various non-lymphoid tissues. Within this chapter, detailed protocols are presented that allow for the generation of single-cell suspensions from mouse lymphohematopoietic tissues including spleen, peripheral lymph nodes, and thymus, with a focus on the subsequent analysis of DC by flow cytometry. However, prepared single-cell suspensions can be subjected to other applications including sorting and cellular enrichment procedures, RNA sequencing, Western blotting, and many more. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.
Created from Fastlane, Scopus look-up
Keywords: dendritic cells; high-parameter flow cytometry; mouse lymphoid tissues; myeloid cells; single-cell suspension preparation

Guidelines for DC preparation and flow cytometry analysis of mouse nonlymphoid tissues - Probst, Hans Christian; Stoitzner, Patrizia; Amon, Lukas; Backer, Ronald A.; Brand, Anna; Chen, Jianzhou; Clausen, Björn E.; Dieckmann, Sophie; Dudziak, Diana; Heger, Lukas; Hodapp, Katrin; Hornsteiner, Florian; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various nonlymphoid tissues. DC are sentinels of the immune system present in almost every mammalian organ. Since they represent a rare cell population, DC need to be extracted from organs with protocols that are specifically developed for each tissue. This article provides detailed protocols for the preparation of single-cell suspensions from various mouse nonlymphoid tissues, including skin, intestine, lung, kidney, mammary glands, oral mucosa and transplantable tumors. Furthermore, our guidelines include comprehensive protocols for multiplex flow cytometry analysis of DC subsets and feature top tricks for their proper discrimination from other myeloid cells. With this collection, we provide guidelines for in-depth analysis of DC subsets that will advance our understanding of their respective roles in healthy and diseased tissues. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all coauthors, making it an essential resource for basic and clinical DC immunologists.
Created from Fastlane, Scopus look-up
Keywords: Dendritic cells; Discrimination of dendritic cell subsets; Mouse nonlymphoid tissue; Multiplex flow cytometry analysis; Tissue digestion protocols

Guidelines for mouse and human DC functional assays - Clausen, Bjoern E.; Amon, Lukas; Backer, Ronald A.; Berod, Luciana; Bopp, Tobias; Brand, Anna; Burgdorf, Sven; Chen, Luxia; Da, Meihong; Distler, Ute; Dress, Regine J.; Dudziak, Diana; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. Recent studies have provided evidence for an increasing number of phenotypically distinct conventional DC (cDC) subsets that on one hand exhibit a certain functional plasticity, but on the other hand are characterized by their tissue- and context-dependent functional specialization. Here, we describe a selection of assays for the functional characterization of mouse and human cDC. The first two protocols illustrate analysis of cDC endocytosis and metabolism, followed by guidelines for transcriptomic and proteomic characterization of cDC populations. Then, a larger group of assays describes the characterization of cDC migration in vitro, ex vivo, and in vivo. The final guidelines measure cDC inflammasome and antigen (cross)-presentation activity. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.<br

Guidelines for mouse and human DC generation - Lutz, Manfred B.; Ali, Shafaqat; Audiger, Cindy; Autenrieth, Stella E.; Berod, Luciana; Bigley, Venetia; Cyran, Laura; Dalod, Marc; Dörrie, Jan; Dudziak, Diana; Florez-Grau, Georgina; Giusiano, Lucila; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. This article provides protocols with top ticks and pitfalls for preparation and successful generation of mouse and human DC from different cellular sources, such as murine BM and HoxB8 cells, as well as human CD34(+) cells from cord blood, BM, and peripheral blood or peripheral blood monocytes. We describe murine cDC1, cDC2, and pDC generation with Flt3L and the generation of BM-derived DC with GM-CSF. Protocols for human DC generation focus on CD34(+) cell culture on OP9 cell layers for cDC1, cDC2, cDC3, and pDC subset generation and DC generation from peripheral blood monocytes (MoDC). Additional protocols include enrichment of murine DC subsets, CRISPR/Cas9 editing, and clinical grade human DC generation. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.
CRIS-Team WoS Importer:2022-11-11

Guidelines for the use of flow cytometry and cell sorting in immunological studies (second edition) - Cossarizza, Andrea; Acs, Andreas; Adam, Dieter; Adam-Klages, Sabine; Agace, William W.; Aghaeepour, Nima; Akdis, Mübeccel; Allez, Matthieu; Almeida, Larissa Nogueira; Alvisi, Giorgia; Anderson, Graham; Andrä, Immanuel; et al. (European Journal of Immunology, 2019)
These guidelines are a consensus work of a considerable number of members of the immunology and flow cytometry community. They provide the theory and key practical aspects of flow cytometry enabling immunologists to avoid the common errors that often undermine immunological data. Notably, there are comprehensive sections of all major immune cell types with helpful Tables detailing phenotypes in murine and human cells. The latest flow cytometry techniques and applications are also described, featuring examples of the data that can be generated and, importantly, how the data can be analysed. Furthermore, there are sections detailing tips, tricks and pitfalls to avoid, all written and peer-reviewed by leading experts in the field, making this an essential research companion.
CRIS-Team Scopus Importer:2019-10-29

Harnessing the complete repertoire of conventional dendritic cell functions for cancer immunotherapy - Amon, Lukas; Hatscher, Lukas; Heger, Lukas; Dudziak, Diana; Lehmann, Christian (Pharmaceutics, 2020)
The onset of checkpoint inhibition revolutionized the treatment of cancer. However, studies from the last decade suggested that the sole enhancement of T cell functionality might not suffice to fight malignancies in all individuals. Dendritic cells (DCs) are not only part of the innate immune system, but also generals of adaptive immunity and they orchestrate the de novo induction of tolerogenic and immunogenic T cell responses. Thus, combinatorial approaches addressing DCs and T cells in parallel represent an attractive strategy to achieve higher response rates across patients. However, this requires profound knowledge about the dynamic interplay of DCs, T cells, other immune and tumor cells. Here, we summarize the DC subsets present in mice and men and highlight conserved and divergent characteristics between different subsets and species. Thereby, we supply a resource of the molecular players involved in key functional features of DCs ranging from their sentinel function, the translation of the sensed environment at the DC:T cell interface to the resulting specialized T cell effector modules, as well as the influence of the tumor microenvironment on the DC function. As of today, mostly monocyte derived dendritic cells (moDCs) are used in autologous cell therapies after tumor antigen loading. While showing encouraging results in a fraction of patients, the overall clinical response rate is still not optimal. By disentangling the general aspects of DC biology, we provide rationales for the design of next generation DC vaccines enabling to exploit and manipulate the described pathways for the purpose of cancer immunotherapy in vivo. Finally, we discuss how DC-based vaccines might synergize with checkpoint inhibition in the treatment of malignant diseases.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Antigen targeting; Cancer therapy; Checkpoint inhibition; Dendritic cells; Pattern recognition receptors; T cells; Tumor microenvironment; Vaccination

Harnessing the Participation of Dendritic Cells in Immunity and Tolerance - Boscardin, Silvia Beatriz; Dudziak, Diana; Muenz, Christian; Rosa, Daniela Santoro (Frontiers in Immunology, 2020)
CRIS-Team Scopus Importer:2020-11-13
Keywords: antigen presentation; DC subtypes; dendritic cell; dendritic cell activation; dendritic cell vaccine therapy

Have We Ignored Vector-Associated Microbiota While Characterizing the Function of Langerhans Cells in Experimental Cutaneous Leishmaniasis? - Nerb, Benedikt; Dudziak, Diana; Gessner, André; Feuerer, Markus; Ritter, Uwe (Frontiers in Tropical Diseases, 2022)
CRIS-Team Scopus Importer:2024-12-16
Keywords: dendritic cells; experimental cutaneous leishmaniasis; Langerhans cells; lymph node; microbiome; skin; T cell-mediated immunity

Heterogeneity and function of conventional dendritic cells from early to adult life - Schraml, B.; Papaioannou, N.; Shakiba, R.; Ravi, K.; Kuentzel, V.; Salei, N.; Lehman, C. H.; Fiancette, R.; Messerer, D.; Ohnmacht, C.; Haller, D.; Staub, T.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Human Fcγ-receptor IIb modulates pathogen-specific versus self-reactive antibody responses in lyme arthritis - Danzer, Heike; Glaesner, Joachim; Baerenwaldt, Anne; Reitinger, Carmen; Lux, Anja; Heger, Lukas; Dudziak, Diana; Harrer, Thomas; Gessner, Andre; Nimmerjahn, Falk (eLife, 2020)
Pathogen-specific antibody responses need to be tightly regulated to generate protective but limit self-reactive immune responses. While loss of humoral tolerance has been associated with microbial infections, the pathways involved in balancing protective versus autoreactive antibody responses in humans are incompletely understood. Studies in classical mouse model systems have provided evidence that balancing of immune responses through inhibitory receptors is an important quality control checkpoint. Genetic differences between inbred mouse models and the outbred human population and allelic receptor variants not present in mice; however, argue for caution when directly translating these findings to the human system. By studying Borrelia burgdorferi infection in humanized mice reconstituted with human hematopoietic stem cells from donors homozygous for a functional or a non-functional FcγRIIb allele, we show that the human inhibitory FcγRIIb is a critical checkpoint balancing protective and autoreactive immune responses, linking infection with induction of autoimmunity in the human immune system.
CRIS-Team Scopus Importer:2020-09-11
Keywords: arthritis; autoimmunity; borrelia burgdorferi; Fc-receptor; humanized mouse; immunology; inflammation; mouse

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, Jil; Lehmann, Christian; Heger, Lukas; Eissing, Nathalie; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (Science immunology, 2016)
In mice, conventional and plasmacytoid dendritic cells (DCs) derive from separate hematopoietic precursors before they migrate to peripheral tissues. Moreover, two classes of conventional DCs (cDC1 and cDC2 DCs) and one class of plasmacytoid DCs (pDCs) have been shown to be transcriptionally and functionally distinct entities. In humans, these three DC subtypes can be identified using the cell surface markers CD1c (cDC2), CD141 (cDC1), and CD303 (pDCs), albeit it remains elusive whether DC functionality is mainly determined by ontogeny or the tissue microenvironment. By phenotypic and transcriptional profiling of these three DC subtypes in different human tissues derived from a large number of human individuals, we demonstrate that DC subpopulations in organs of the lymphohematopoietic system (spleen, thymus, and blood) are strongly defined by ontogeny rather than by signals from the microenvironment. In contrast, DC subsets derived from human lung or skin differed substantially, strongly arguing that DCs react toward modulatory signals from tissue microenvironments. Collectively, the data obtained in this study may serve as a major resource to guide further studies into human DC biology during homeostasis and inflammatio
EVALuna2:6852

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, J.; Lehmann, C. H. K.; Heger, Lukas; Eissing, N.; Baranska, A.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (2017)
EVALuna2:33137

Identification and characterization of the specific murine NK cell subset supporting graft-versus-leukemia- and reducing graft-versus-host-effects - Meinhardt, Kathrin; Kroeger, Irena; Bauer, Ruth; Ganss, Franziska; Ovsiy, Ilja; Rothamer, Johanna; Büttner, Maike; Atreya, Imke; Waldner, Maximilian; Bittrich, Max; Lehmann, Christian; Rieger, Michael A.; et al. (OncoImmunology, 2015)
Clinical studies investigating the impact of natural killer (NK) cells in allogeneic hematopoietic stem cell transplantation settings have yielded promising results. However, NK cells are a functionally and phenotypically heterogeneous population. Therefore, we addressed the functional relevance of specific NK cell subsets distinguished by expression of CD117, CD27 and CD11b surface markers in graft-versus-leukemia (GVL)-reaction and graft-versus-host-disease (GVHD). Our results clearly demonstrate that the subset of c-Kit(-)CD27(-)CD11b(+) NK cells expressed multiple cytotoxic pathway genes and provided optimal graft-versus-leukemia-effects, while significantly reducing T cell proliferation induced by allogeneic dendritic cells. Furthermore, these NK cells migrated to inflamed intestinal tissues where graft-versus-host-colitis was efficiently mitigated. For the first time, we identified the c-Kit(-)CD27(-)CD11b(+) NK cell population as the specific effector NK cell subset capable of significantly diminishing GVHD in fully mismatched bone marrow transplantation settings. In conclusion, the subset of c-Kit(-)CD27(-)CD11b(+) NK cells not only supports GVL, but also plays a unique role in the protection against GVHD by migrating to the peripheral GVHD target organs where they exert efficient immunoregulatory activities. These new insights demonstrate the importance of selecting the optimal NK cell subset for cellular immunotherapy following allogeneic hematopoietic stem cell transplantation.
EVALuna2:1965

Identification of Novel STAT6-Regulated Proteins in Mouse B Cells by Comparative Transcriptome and Proteome Analysis - Mokada Gopal, Lavanya; Boeser, Alexander; Lehmann, Christian; Drepper, Friedel; Dudziak, Diana; Warscheid, Bettina; Vöhringer, David (Journal of Immunology, 2017)
The transcription factor STAT6 plays a key role in mediating signaling downstream of the receptors for IL-4 and IL-13. In B cells, STAT6 is required for class switch recombination to IgE and for germinal center formation during type 2 immune responses directed against allergens or helminths. In this study, we compared the transcriptomes and proteomes of primary mouse B cells from wild-type and STAT6-deficient mice cultured for 4 d in the presence or absence of IL-4. Microarray analysis revealed that 214 mRNAs were upregulated and 149 were downregulated >3-fold by IL-4 in a STAT6-dependent manner. Across all samples, 5000 proteins were identified by label-free quantitative liquid chromatography/mass spectrometry. A total of 149 proteins was found to be differentially expressed >3-fold between IL-4-stimulated wild-type and STAT6(-/-) B cells (75 upregulated and 74 downregulated). Comparative analysis of the proteome and transcriptome revealed that expression of these proteins was mainly regulated at the transcriptional level, which argues against a major role for posttranscriptional mechanisms that modulate the STAT6-dependent proteome. Nine proteins were selected for confirmation by flow cytometry or Western blot. We show that CD30, CD79b, SLP-76, DEC205, IL-5R?, STAT5, and Thy1 are induced by IL-4 in a STAT6-dependent manner. In contrast, Syk and Fc receptor-like 1 were downregulated. This dataset provides a framework for further functional analysis of newly identified IL-4-regulated proteins in B cells that may contribute to germinal center formation and IgE switching in type 2 immunity.
EVALuna2:25886

Ileal immune tonus is a prognosis marker of proximal colon cancer in mice and patients - Picard, Marion; Yonekura, Satoru; Slowicka, Karolina; Petta, Ioanna; Rauber, Conrad; Routy, Bertrand; Richard, Corentin; Iebba, Valerio; Tidjani Alou, Maryam; Becharef, Sonia; Ly, Pierre; Pizzato, Eugenie; et al. (Cell Death and Differentiation, 2020)
Ileal epithelial cell apoptosis and the local microbiota modulate the effects of oxaliplatin against proximal colon cancer by modulating tumor immunosurveillance. Here, we identified an ileal immune profile associated with the prognosis of colon cancer and responses to chemotherapy. The whole immune ileal transcriptome was upregulated in poor-prognosis patients with proximal colon cancer, while the colonic immunity of healthy and neoplastic areas was downregulated (except for the Th17 fingerprint) in such patients. Similar observations were made across experimental models of implanted and spontaneous murine colon cancer, showing a relationship between carcinogenesis and ileal inflammation. Conversely, oxaliplatin-based chemotherapy could restore a favorable, attenuated ileal immune fingerprint in responders. These results suggest that chemotherapy inversely shapes the immune profile of the ileum–tumor axis, influencing clinical outcome.
CRIS-Team Scopus Importer:2020-12-11

Immunoglobulin G-dependent inhibition of inflammatory bone remodeling requires pattern recognition receptor Dectin-1 - Seeling, Michaela; Pöhnl, Matthias; Kara, Sibel; Horstmann, Nathalie; Riemer, Carolina; Wöhner, Miriam; Liang, Chunguang; Brückner, Christin; Eiring, Patrick; Werner, Anja; Biburger, Markus; Altmann, Leon; et al. (Immunity, 2023)
Immunoglobulin G (IgG) antibodies are major drivers of inflammation during infectious and autoimmune diseases. In pooled serum IgG (IVIg), however, antibodies have a potent immunomodulatory and anti-inflammatory activity, but how this is mediated is unclear. We studied IgG-dependent initiation of resolution of inflammation in cytokine- and autoantibody-driven models of rheumatoid arthritis and found IVIg sialylation inhibited joint inflammation, whereas inhibition of osteoclastogenesis was sialic acid independent. Instead, IVIg-dependent inhibition of osteoclastogenesis was abrogated in mice lacking receptors Dectin-1 or FcγRIIb. Atomistic molecular dynamics simulations and super-resolution microscopy revealed that Dectin-1 promoted FcγRIIb membrane conformations that allowed productive IgG binding and enhanced interactions with mouse and human IgG subclasses. IVIg reprogrammed monocytes via FcγRIIb-dependent signaling that required Dectin-1. Our data identify a pathogen-independent function of Dectin-1 as a co-inhibitory checkpoint for IgG-dependent inhibition of mouse and human osteoclastogenesis. These findings may have implications for therapeutic targeting of autoantibody and cytokine-driven inflammation.
CRIS-Team Scopus Importer:2023-05-12
Keywords: bone; Dectin-1; Fc-receptor; glycosylation; IgG; inflammation; osteoclast; rheumatoid arthritis

Impact of Plasma Membrane Domains on IgG Fc Receptor Function - Kara, Sibel; Amon, Lukas; Lühr, Jennifer; Nimmerjahn, Falk; Dudziak, Diana; Lux, Anja (Frontiers in Immunology, 2020)
Lipid cell membranes not only represent the physical boundaries of cells. They also actively participate in many cellular processes. This contribution is facilitated by highly complex mixtures of different lipids and incorporation of various membrane proteins. One group of membrane-associated receptors are Fc receptors (FcRs). These cell-surface receptors are crucial for the activity of most immune cells as they bind immunoglobulins such as immunoglobulin G (IgG). Based on distinct mechanisms of IgG binding, two classes of Fc receptors are now recognized: the canonical type I FcγRs and select C-type lectin receptors newly referred to as type II FcRs. Upon IgG immune complex induced cross-linking, these receptors are known to induce a multitude of cellular effector responses in a cell-type dependent manner, including internalization, antigen processing, and presentation as well as production of cytokines. The response is also determined by specific intracellular signaling domains, allowing FcRs to either positively or negatively modulate immune cell activity. Expression of cell-type specific combinations and numbers of receptors therefore ultimately sets a threshold for induction of effector responses. Mechanistically, receptor cross-linking and localization to lipid rafts, i.e., organized membrane microdomains enriched in intracellular signaling proteins, were proposed as major determinants of initial FcR activation. Given that immune cell membranes might also vary in their lipid compositions, it is reasonable to speculate, that the cell membrane and especially lipid rafts serve as an additional regulator of FcR activity. In this article, we aim to summarize the current knowledge on the interplay of lipid rafts and IgG binding FcRs with a focus on the plasma membrane composition and receptor localization in immune cells, the proposed mechanisms underlying this localization and consequences for FcR function with respect to their immunoregulatory capacity.
CRIS-Team Scopus Importer:2020-07-24
Keywords: cell membrane; CLR; FcγR; lipid rafts; membrane; membrane localization; type I FcR; type II FcR

IMPACT OF TOLL-LIKE RECEPTOR 9 IN INFLAMMATORY ARTHRITIS AND OSTEOCLASTOGENESIS - Fischer, Anita; Boehm, Christina; Koenders, Marije; Van Den Berg, Wim; Rothe, Tobias; Krönke, Gerhard; Dudziak, Diana; Steiner, Guenter (2017)
EVALuna2:34374

Induction of anti-tumor responses via antigen targeting of dendritic cells in vivo - Amon, Lukas; Lehmann, Christian; Baranska, A.; Heidkamp, Gordon Frederik; Heger, Lukas; Lühr, Jennifer; Hofmann, Andrea; Nimmerjahn, Falk; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Inflammasomes in dendritic cells: Friend or foe? - Hatscher, Lukas; Amon, Lukas; Heger, Lukas; Dudziak, Diana (Immunology Letters, 2021)
Inflammasomes are cytosolic multiprotein complexes that crucially contribute to host defense against pathogens but are also involved in the pathogenesis of autoinflammatory diseases. Inflammasome formation leads to activation of effector caspases (caspase-1, 4, 5, or 11), the proteolytic maturation of IL-1β and IL-18 as well as cleavage of the pore-forming protein Gasdermin D. Dendritic cells are major regulators of immune responses as they bridge innate and adaptive immunity. We here summarize the current knowledge on inflammasome expression and formation in murine bone marrow-, human monocyte-derived as well as murine and human primary dendritic cells. Further, we discuss both, the beneficial and detrimental, involvement of inflammasome activation in dendritic cells in cancer, infections, and autoimmune diseases. As inflammasome activation is typically accompanied by Gasdermin D-mediated pyroptosis, which is an inflammatory form of programmed cell death, inflammasome formation in dendritic cells seems ill-advised. Therefore, we propose that hyperactivation, which is inflammasome activation without the induction of pyroptosis, may be a general model of inflammasome activation in dendritic cells to enhance Th1, Th17 as well as cytotoxic T cell responses.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Dendritic cell; Hyperactivation; Inflammasome; NLRP3; T cell response; Vaccination

In vivo enzymatic modulation of IgG glycosylation inhibits autoimmune disease in an IgG subclass-dependent manner. - Albert, Heike; Collin, Mattias; Dudziak, Diana; Ravetch, J. V.; Nimmerjahn, Falk (Proceedings of the National Academy of Sciences of the United States of America, 2008)
IgG antibodies are potent inducers of proinflammatory responses. During autoimmune diseases such as arthritis and systemic lupus erythematosus, IgG autoantibodies are responsible for the chronic inflammation and destruction of healthy tissues by cross-linking Fc receptors on innate immune effector cells. The sugar moiety attached to the asparagine-297 residue in the constant domain of the antibody is critical for the overall structure and function of the molecule. Removal of this sugar domain leads to the loss of the proinflammatory activity, suggesting that in vivo modulation of antibody glycosylation might be a strategy to interfere with autoimmune processes. In this work, we investigated whether removal of the majority of the IgG-associated sugar domain by endoglycosidase S (EndoS) from Streptococcus pyogenes is able to interfere with autoimmune inflammation. We demonstrate that EndoS injection efficiently removes the IgG-associated sugar domain in vivo and interferes with autoantibody-mediated proinflammatory processes in a variety of autoimmune models. Importantly, however, we observed a differential impact of EndoS-mediated sugar side chain hydrolysis on IgG activity depending on the individual IgG subclass.

Kit regulates HSC engraftment across the human-mouse species barrier - Cosgun, Kadriye Nehir; Rahmig, Susann; Mende, Nicole; Reinke, Soeren; Hauber, Ilona; Schaefer, Carola; Petzold, Anke; Weisbach, Henry; Heidkamp, Gordon Frederik; Purbojo, Ariawan; Cesnjevar, Robert; Platz, Alexander; et al. (Cell Stem Cell, 2014)
In-depth analysis of the cellular and molecular mechanisms regulating human HSC function will require a surrogate host that supports robust maintenance of transplanted human HSCs in vivo, but the currently available options are problematic. Previously we showed that mutations in the Kit receptor enhance engraftment of transplanted HSCs in the mouse. To generate an improved model for human HSC transplantation and analysis, we developed immune-deficient mouse strains containing Kit mutations. We found that mutation of the Kit receptor enables robust, uniform, sustained, and serially transplantable engraftment of human HSCs in adult mice without a requirement for irradiation conditioning. Using this model, we also showed that differential KIT expression identifies two functionally distinct subpopulations of human HSCs. Thus, we have found that the capacity of this Kit mutation to open up stem cell niches across species barriers has significant potential and broad applicability in human HSC research.
EVALuna2:19491

Lenalidomide enhances MOR202-dependent macrophage-mediated effector functions via the vitamin D pathway - Busch, Leonhard; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Müller, Miriam J.; Volmer, Dietrich A.; Bach, Christian; Fabri, Mario; Bittenbring, Jörg T.; Neumann, Frank; Boxhammer, Rainer; Nolting, Jens; Bisht, Savita; et al. (Leukemia, 2018)
Macrophages are key mediators of the therapeutic effects exerted by monoclonal antibodies, such as the anti-CD38 antibody MOR202, currently introduced in multiple myeloma (MM) therapy. Therefore, it is important to understand how antibody-mediated effector functions of myeloma-associated macrophages (MAMs) are regulated. Here, we focused on the effects of vitamin D, a known regulator of macrophage effector functions. Consequently, it was the aim of this study to assess whether modulation of the vitamin D pathway alters the tumoricidal activity of MAMs. Here, we demonstrate that MAMs display a defective vitamin D pathway with reduced expression level of CYP27B1 and limited tumoricidal activity which can be restored by the IMiD lenalidomide in vitro. Furthermore, our data indicate that the vitamin D pathway of MAMs from MM patients does recover during an IMiD-containing therapy shown by an improved MOR202-mediated cytotoxic activity of these MAMs against primary MM cells ex vivo. Here, the ex vivo cytotoxic activity could be further enhanced by vitamin D supplementation. These data suggest that vitamin D holds a key role for the effector functions of MAMs and that vitamin D supplementation in IMiD combination trials could further increase the therapeutic efficacy of anti-CD38 antibodies such as MOR202, which remains to be investigated in clinical studies.
EVALuna2:34165

Loading of Primary Human T Lymphocytes with Citrate-Coated Superparamagnetic Iron Oxide Nanoparticles Does Not Impair Their Activation after Polyclonal Stimulation - Mühlberger, Marina; Unterweger, Harald; Band, Julia; Lehmann, Christian; Heger, Lukas; Dudziak, Diana; Alexiou, Christoph; Lee, Geoffrey; Janko, Christina (Cells, 2020)
For the conversion of immunologically cold tumors, characterized by a low T cell infiltration, into hot tumors, it is necessary to enrich T cells in the tumor area. One possibility is the use of magnetic fields to direct T cells into the tumor. For this purpose, primary T cells that were freshly isolated from human whole blood were loaded with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONCitrate). Cell toxicity and particle uptake were investigated by flow cytometry and atomic emission spectroscopy. The optimum loading of the T cells without any major effect on their viability was achieved with a particle concentration of 75 mu g Fe/mL and a loading period of 24 h. The cellular content of SPIONCitrate was sufficient to attract these T cells with a magnet which was monitored by live-cell imaging. The functionality of the T cells was only slightly influenced by SPIONCitrate, as demonstrated by in vitro stimulation assays. The proliferation rate as well as the expression of co-stimulatory and inhibitory surface molecules (programmed cell death 1 (PD-1), lymphocyte activation gene 3 (LAG-3), T cell immunoglobulin and mucin domain containing 3 (Tim-3), C-C motif chemokine receptor 7 (CCR7), CD25, CD45RO, CD69) was investigated and found to be unchanged. Our results presented here demonstrate the feasibility of loading primary human T lymphocytes with superparamagnetic iron oxide nanoparticles without influencing their viability and functionality while achieving sufficient magnetizability for magnetically controlled targeting. Thus, the results provide a strong fundament for the transfer to tumor models and ultimately for new immunotherapeutic approaches for cancer treatment.
CRIS-Team WoS Importer:2020-04-21

Mast-Cell-Derived TNF Amplifies CD8(+) Dendritic Cell Functionality and CD8(+) T Cell Priming - Dudeck, Jan; Ghouse, Shanawaz Mohammed; Lehmann, Christian; Hoppe, Anja; Schubert, Nadja; Nedospasov, Sergei A.; Dudziak, Diana; Dudeck, Anne (Cell Reports, 2015)
Mast cells are critical promoters of adaptive immunity in the contact hypersensitivity model, but the mechanism of allergen sensitization is poorly understood. Using Mcpt5-CreTNF(FL/FL) mice, we show here that the absence of TNF exclusively in mast cells impaired the expansion of CD8(+) T cells upon sensitization and the T-cell-driven adaptive immune response to elicitation. T cells primed in the absence of mast cell TNF exhibited a diminished efficiency to transfer sensitization to naive recipients. Specifically, mast cell TNF promotes CD8(+) dendritic cell (DC) maturation and migration to draining lymph nodes. The peripherally released mast cell TNF further critically boosts the CD8(+) T-cell-priming efficiency of CD8(+) DCs, thereby linking mast cell effects on T cells to DC modulation. Collectively, our findings identify the distinct potential of mast cell TNF to amplify CD8(+) DC functionality and CD8(+) T-cell-dominated adaptive immunity, which may be of great importance for immunotherapy and vaccination approaches.
EVALuna2:19558

Maturation of monocyte-derived DCs leads to increased cellular stiffness, higher membrane fluidity, and changed lipid composition - Lühr, Jennifer; Alex, Nils; Amon, Lukas; Kraeter, Martin; Kubankova, Marketa; Sezgin, Erdinc; Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Smith, Ana-Suncana; Zaburdaev, Vasily; Böckmann, Rainer; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Maturation of Monocyte-Derived DCs Leads to Increased Cellular Stiffness, Higher Membrane Fluidity, and Changed Lipid Composition - Luhr, Jennifer J.; Alex, Nils; Amon, Lukas; Krater, Martin; Kubankova, Marketa; Sezgin, Erdinc; Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Smith, Ana-Suncana; Zaburdaev, Vasily; Böckmann, Rainer; et al. (Frontiers in Immunology, 2020)
Dendritic cells (DCs) are professional antigen-presenting cells of the immune system. Upon sensing pathogenic material in their environment, DCs start to mature, which includes cellular processes, such as antigen uptake, processing and presentation, as well as upregulation of costimulatory molecules and cytokine secretion. During maturation, DCs detach from peripheral tissues, migrate to the nearest lymph node, and find their way into the correct position in the net of the lymph node microenvironment to meet and interact with the respective T cells. We hypothesize that the maturation of DCs is well prepared and optimized leading to processes that alter various cellular characteristics from mechanics and metabolism to membrane properties. Here, we investigated the mechanical properties of monocyte-derived dendritic cells (moDCs) using real-time deformability cytometry to measure cytoskeletal changes and found that mature moDCs were stiffer compared to immature moDCs. These cellular changes likely play an important role in the processes of cell migration and T cell activation. As lipids constitute the building blocks of the plasma membrane, which, during maturation, need to adapt to the environment for migration and DC-T cell interaction, we performed an unbiased high-throughput lipidomics screening to identify the lipidome of moDCs. These analyses revealed that the overall lipid composition was significantly changed during moDC maturation, even implying an increase of storage lipids and differences of the relative abundance of membrane lipids upon maturation. Further, metadata analyses demonstrated that lipid changes were associated with the serum low-density lipoprotein (LDL) and cholesterol levels in the blood of the donors. Finally, using lipid packing imaging we found that the membrane of mature moDCs revealed a higher fluidity compared to immature moDCs. This comprehensive and quantitative characterization of maturation associated changes in moDCs sets the stage for improving their use in clinical application.
CRIS-Team Scopus Importer:2020-12-25
Keywords: cell mechanics; cellular stiffness; cholesterol; lipidomics; lipids; low-density lipoprotein; maturation; monocyte-derived dendritic cells

Mechanical Regulation of Epithelial Tissue Homeostasis - Kaliman, Sara; Hubert, Maxime; Wollnik, Carina; Nuic, Lovro; Vurnek, Damir; Gehrer, Simone; Lovrić, Jakov; Dudziak, Diana; Rehfeldt, Florian; Smith, Ana-Suncana (Physical Review X, 2021)
Despite recent efforts to understand homeostasis in epithelial tissues, there are many unknowns surrounding this steady state. It is considered to be regulated by mechanoresponse, but unlike for single cells, this idea remains heavily debated for tissues. Here, we show that changes in matrix stiffness induce a nonequilibrium transition from tubular to squamous Madin-Darby Canine Kidney II tissues. Nonetheless, despite different cell morphologies and densities, all homeostatic tissues display equivalent topologies, which, hence, must be actively targeted and regulated. On the contrary, the mechanoresponse induces dramatic changes in the large-scale organization of the colonies. On stiff gels, this yields an unreported cooperative state of motile cells displaying higher densities than in the arrested homeostatic state, which suggests a more complex relation between cell density and motility than previously anticipated. Our results unequivocally relate the mechanosensitive properties of individual cells to the evolving macroscopic structures, an effect that could be important for understanding the emergent pathologies of living tissues.
CRIS-Team WoS Importer:2021-08-20

Meeting Report: 47th Annual Meeting of the “Arbeitsgemeinschaft Dermatologische Forschung” - Stary, Georg; Fabri, Mario; Gebhardt, Christoffer; Eming, Rüdiger; Matthias, Julia; Vorobyev, Artem; Effern, Maike; Strobl, Johanna; Günther, Claudia; Zielinski, Christina; Dudziak, Diana; Géraud, Cyril; et al. (Experimental Dermatology, 2022)
CRIS-Team Scopus Importer:2022-03-18

Melanocytes as an emerging key player in niche regulation of limbal stem cells - Schlötzer-Schrehardt, Ursula; Polisetti, Naresh; Zenkel, Matthias; Naschberger, Elisabeth; Heger, Lukas; Dudziak, Diana; Stürzl, Michael; Kruse, Friedrich (2018)
EVALuna2:34738

Melanocytes as emerging key players in niche regulation of limbal epithelial stem cells - Polisetti, Naresh; Gießl, Andreas; Zenkel, Matthias; Heger, Lukas; Dudziak, Diana; Naschberger, Elisabeth; Stich, Lena; Steinkasserer, Alexander; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Ocular Surface, 2021)
Purpose: Limbal melanocytes (LMel) represent essential components of the corneal epithelial stem cell niche and are known to protect limbal epithelial stem/progenitor cells (LEPCs) from UV damage by transfer of melanosomes. Here, we explored additional functional roles for LMel in niche homeostasis, immune regulation and angiostasis. Methods: Human corneoscleral tissues were morphologically analyzed in normal, inflammatory and wound healing conditions. The effects of LMel on LEPCs were analyzed in direct and indirect co-culture models using electron microscopy, immunocytochemistry, qRT-PCR, Western blotting and functional assays; limbal mesenchymal stromal cells and murine embryonic 3T3 fibroblasts served as controls. The immunophenotype of LMel was assessed by flow cytometry before and after interferon-γ stimulation, and their immunomodulatory properties were analyzed by mixed lymphocytes reaction, monocyte adhesion assays and cytometric bead arrays. Their angiostatic effects on human umbilical cord endothelial cells (HUVECs) were evaluated by proliferation, migration, and tube formation assays. Results: LMel and LEPCs formed structural units in the human limbal stem cell niche in situ, which could be functionally replicated, including melanosome transfer, by co-cultivation in vitro. LMel supported LEPCs during clonal expansion and during epithelial wound healing by stimulating proliferation and migration, and suppressed their differentiation through direct contact and paracrine effects. Under inflammatory conditions, LMel were increased in numbers and upregulated expression of ICAM-1 and MHC II molecules (HLA-DR), but lacked expression of HLA-G, -DP, -DQ and costimulatory molecules CD80 and CD86. They were also found to be potent suppressors of alloreactive T- cell proliferation and cytokine secretion, which largely depended on direct cell-cell interaction. Moreover, the LMel secretome exerted angiostatic activity by inhibiting vascular endothelial cell proliferation and capillary network formation. Conclusion: These findings suggest that LMel are not only professional melanin-producing cells, but exert various non-canonical functions in limbal niche homeostasis by regulating LEPC maintenance, immune responses, and angiostasis. Their potent regulatory, immunomodulatory and anti-angiogenic properties may have important implications for future regenerative cell therapies.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Angiostasis; Immune regulation; Inflammation; Limbal niche; Limbal stem cells; Melanocytes; Wound healing

Modulation of urelumab glycosylation separates immune stimulatory activity from organ toxicity - Reitinger, Carmen; Ipsen Escobedo, Andrea; Hornung, Chiara; Heger, Lukas; Dudziak, Diana; Lux, Anja; Nimmerjahn, Falk (Frontiers in Immunology, 2022)
Checkpoint control and immunomodulatory antibodies have become important tools for modulating tumor or self-reactive immune responses. A major issue preventing to make full use of the potential of these immunomodulatory antibodies are the severe side-effects, ranging from systemic cytokine release syndrome to organ-specific toxicities. The IgG Fc-portion has been demonstrated to contribute to both, the desired as well as the undesired antibody activities of checkpoint control and immunomodulatory antibodies via binding to cellular Fcγ-receptors (FcγR). Thus, choosing IgG subclasses, such as human IgG4, with a low ability to interact with FcγRs has been identified as a potential strategy to limit FcγR or complement pathway dependent side-effects. However, even immunomodulatory antibodies on the human IgG4 background may interact with cellular FcγRs and show dose limiting toxicities. By using a humanized mouse model allowing to study the immunomodulatory activity of human checkpoint control antibodies in vivo, we demonstrate that deglycosylation of the CD137-specific IgG4 antibody urelumab results in an amelioration of liver toxicity, while maintaining T cell stimulatory activity. In addition, our results emphasize that antibody dosing impacts the separation of side-effects of urelumab from its therapeutic activity via IgG deglycosylation. Thus, glycoengineering of human IgG4 antibodies may be a possible approach to limit collateral damage by immunomodulatory antibodies and allow for a greater therapeutic window of opportunity.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD137; Fc-receptors; glycosylation; therapeutic antibody; urelumab

Monocyte-Derived signals activate human natural Killer cells in response to Leishmania Parasites - Messlinger, Helena; Sebald, Heidi; Heger, Lukas; Dudziak, Diana; Bogdan, Christian; Schleicher, Ulrike (Frontiers in Immunology, 2018)
Activated natural killer (NK) cells release interferon (IFN)-gamma, which is crucial for the control of intracellular pathogens such as Leishmania. In contrast to experimental murine leishmaniasis, the human NK cell response to Leishmania is still poorly characterized. Here, we investigated the interaction of human blood NK cells with promastigotes of different Leishmania species (Leishmania major, Leishmania mexicana, Leishmania infantum, and Leishmania donovani). When peripheral blood mononuclear cells or purified NK cells and monocytes (all derived from healthy blood donors from Germany without a history of leishmaniasis) were exposed to promastigotes, NK cells showed increased surface expression of the activation marker CD69. The extent of this effect varied depending on the Leishmania species; differences between dermotropic and viscerotropic L. infantum strains were not observed. Upregulation of CD69 required direct contact between monocytes and Leishmania and was partly inhibitable by anti-interleukin (IL)-18. Unexpectedly, IL-18 was undetectable in most of the supernatants (SNs) of monocyte/parasite cocultures. Confocal fluorescence microscopy of non-permeabilized cells revealed that Leishmania-infected monocytes trans-presented IL-18 to NK cells. Native, but not heat-treated SNs of monocyte/Leishmania cocultures also induced CD69 on NK cells, indicating the involvement of a soluble heat-labile factor other than IL-18. A role for the NK cell-activating cytokines IL-1 beta, IL-2, IL-12, IL-15, IL-21, and IFN-alpha/beta was excluded. The increase of CD69 was not paralleled by NK cell IFN-gamma production or enhanced cytotoxicity. However, prior exposure of NK cells to Leishmania parasites synergistically increased their IFN-gamma release in response to IL-12, which was dependent on endogenous IL-18. CD1c(+) dendritic cells were identified as possible source of Leishmania-induced IL-12. Finally, we observed that direct contact between Leishmania and NK cells reduced the expression of CD56 mRNA and protein on NK cells. We conclude that Leishmania activate NK cells via trans-presentation of IL-18 by monocytes and by a monocyte-derived soluble factor. IL-12 is needed to elicit the IFN-gamma-response of NK cells, which is likely to be an important component of the innate control of the parasite.
EVALuna2:33305

Monocytes Elicit a Neutrophil-Independent Th1/Th17 Response Upon Immunization With a Mincle-Dependent Glycolipid Adjuvant - Desel, Christiane; Murray, Peter J.; Lehmann, Christian; Heger, Lukas; Christensen, Dennis; Andersen, Peter; Mack, Matthias; Dudziak, Diana; Lang, Roland (Frontiers in Immunology, 2022)
Successful subunit vaccination with recombinant proteins requires adjuvants. The glycolipid trehalose-dibehenate (TDB), a synthetic analog of the mycobacterial cord factor, potently induces Th1 and Th17 immune responses and is a candidate adjuvant for human immunization. TDB binds to the C-type lectin receptor Mincle and triggers Syk-Card9-dependent APC activation. In addition, interleukin (IL)-1 receptor/MyD88-dependent signaling is required for TDB adjuvanticity. The role of different innate immune cell types in adjuvant-stimulated Th1/Th17 responses is not well characterized. We investigated cell recruitment to the site of injection (SOI) and to the draining lymph nodes (dLNs) after immunization with the TDB containing adjuvant CAF01 in a protein-based vaccine. Recruitment of monocytes and neutrophils to the SOI and the dramatic increase in lymph node cellularity was partially dependent on both Mincle and MyD88. Despite their large numbers at the SOI, neutrophils were dispensable for the induction of Th1/Th17 responses. In contrast, CCR2-dependent monocyte recruitment was essential for the induction of Th1/Th17 cells. Transport of adjuvant to the dLN did not require Mincle, MyD88, or CCR2. Together, adjuvanticity conferred by monocytes can be separated at the cellular level from potential tissue damage by neutrophils.
CRIS-Team WoS Importer:2022-06-03

Monocyte Subsets Responsible for Immunoglobulin G-Dependent Effector Functions In Vivo - Biburger, Markus; Aschermann, Susanne; Schwab, Inessa; Lux, Anja; Albert, Heike; Danzer, Heike; Woigk, Melissa; Dudziak, Diana; Nimmerjahn, Falk (Immunity, 2011)
Immunoglobulin G (IgG) antibodies confer protection against pathogenic microorganisms, serve as therapeutics in tumor therapy, and are involved in destruction of healthy tissues during autoimmune diseases. Understanding the molecular pathways and effector cell types involved in antibody-mediated effector functions is a prerequisite to modulate these activities. In this study we used two independent model systems to identify innate immune effector cells required for IgG activity in vivo. We first defined the precise repertoire of receptors for the IgG Fc fragment (FcγR) on innate immune effector cells in the blood and on tissue-resident macrophage populations. Despite expression of relevant activating FcγRs on various phagocyte populations, our data indicate that the majority of these cell types are dispensable for IgG activity in vivo. In contrast, IgG-dependent effector functions were selectively impaired in animals lacking the CX CR1 Ly6C CD11c monocyte subset, which expressed the full set of FcγRs required for IgG activity. © 2011 Elsevier Inc.

Morphology as indicator of adaptive changes of model tissues in osmotically and chemically changing environments - Höllring, Kevin; Vurnek, Damir; Gehrer, Simone; Dudziak, Diana; Hubert, Maxime; Smith, Ana-Suncana (Biomaterials Advances, 2023)
We investigate the formation and maintenance of the homeostatic state in the case of 2D epithelial tissues following an induction of hyperosmotic conditions, using media enriched with 80 to 320 mOsm of mannitol, NaCl, and urea. We characterise the changes in the tissue immediately after the osmotic shock, and follow it until the new homeostatic state is formed. We characterise changes in cooperative motility and proliferation pressure in the tissue upon treatment with the help of a theoretical model based on the delayed Fisher-Kolmogorov formalism, where the delay in density evolution is induced by the the finite time of the cell division. Finally we explore the adaptation of the homeostatic tissue to highly elevated osmotic conditions by evaluating the morphology and topology of cells after 20 days in incubation. We find that hyperosmotic environments together with changes in the extracellular matrix induce different mechanical states in viable tissues, where only some remain functional. The perspective is a relation between tissue topology and function, which could be explored beyond the scope of this manuscript. Experimental investigation of morphological effect of change of osmotic conditions on long-term tissue morphology and topology Effect of osmotic changes on transient tissue growth behaviour Analysis of recovery process of tissues post-osmotic-shock Toxicity limits of osmolytes in mid- to long-term tissue evolution Tissue adaptation to physiological changes in environment Long-term tissue stabilisation under altered osmotic conditions.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Epithelium topology and morphology; Fisher-Kolmogorov theory; Hyperosmotic conditions; Model tissue development; Tissue adaptation

Multi-Epitope DC Vaccines with Melanoma Antigens for Immunotherapy of Melanoma - Seretis, Athanasios; Amon, Lukas; Tripp, Christoph H.; Cappellano, Giuseppe; Hornsteiner, Florian; Dieckmann, Sophie; Vierthaler, Janine; Ortner-Tobider, Daniela; Kanduth, Markus; Steindl, Rita; Boon, Louis; den Haan, Joke M.M.; et al. (Vaccines, 2025)
Background/Objectives: The revolution for the treatment of melanoma came with the approval of checkpoint blockade antibodies. However, a substantial proportion of patients show primary or secondary resistance to this type of immunotherapy, indicating the need for alternative therapeutic strategies. Dendritic cells (DCs) of the skin are prime targets for vaccination approaches due to their potential to prime naïve T cells and their accessibility. This study aimed to develop and evaluate novel vaccines targeting the C-type lectin receptor DEC-205 to deliver melanoma-associated antigenic peptides to skin DCs. Methods: We cloned MHC-I-restricted peptides from the glycoprotein (gp)10025–33 and Tyrosinase-related protein (trp)2180–188 into the DEC-205 antibody sequence with modified peptide cutting sites from the OVA257–264 SIINFEKL peptide. We tested their potential to induce CD8+ T cell responses in both in vitro and in vivo settings. Tumor growth inhibition was evaluated in the transplantable B16.OVA melanoma murine model using a multi-epitope DC-based vaccine combining both peptides. Results: The cross-presentation of both gp100 and trp2 peptides was confirmed in vivo when peptide sequences were flanked by the OVA257–264 peptide cutting sites. Moreover, the combination of both antigenic peptides into a multi-epitope DC vaccine was required to inhibit B16.OVA melanoma growth. Conclusions: Our findings suggest that a DC-targeted vaccination approach using multiple epitopes deriving from melanoma antigens could represent a promising strategy for melanoma therapy.
CRIS-Team Scopus Importer:2025-05-09
Keywords: C-type lectin receptors; DC-targeted therapy; dendritic cells; immunotherapy; melanoma antigens

Non-magnetic chromatographic separation of colloidally metastable superparamagnetic iron oxide nanoparticles and suspension cells - Mühlberger, Marina; Janko, Christina; Unterweger, Harald; Band, Julia; Schreiber, Eveline; Lehmann, Christian; Dudziak, Diana; Lee, Geoffrey; Alexiou, Christoph; Tietze, Rainer (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2019)
For magnetic control of cells for biomedical applications such as targeting of immune cells to tumors, cells must be magnetizable. For that, cells are incubated with superparamagnetic iron oxide nanoparticles (SPIONs)to take them up and thus become magnetizable. When using adherent cells, non-ingested SPIONs can be easily removed by rinsing of the particles regardless of their colloidal stability in cell culture medium. However, if suspension cells such as T cells are to be loaded with SPIONs, established methods to separate excess nanoparticles from cells are based on physicochemical parameters such as density, size or magnetizability. Thus, colloidal stability of the particles is of great importance, since only colloidally stable SPIONs can be completely separated from the cells due to their physicochemical differences. Aggregates of colloidally meta- or unstable particles cannot, however, be separated from cells due to their overlapping sizes and densities. Thus, development of an alternative method for the separation of nanoparticle aggregates from suspension cells is urgently needed. Here, we present an affinity chromatographic separation method based on immunohistochemical properties of the respective cells. A desthiobiotinylated antibody against a cellular surface antigen (here CD90.2 receptor on EL4 T cells)is immobilized on a streptavidin agarose column optimized for cell purification. Subsequently the column is loaded with the particle/cell suspension so that the cells bind to the column. After removing the particles by washing, the cells can be gently eluted with biotin solution under physiological conditions. This allows >95% of the excess iron concentration to be removed while maintaining cell viability.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Affinity chromatography; Antibody; Biotin; Cell viability; Desthiobiotin; Streptavidin

Oligoclonal CD4+CXCR5+ T cells with a cytotoxic phenotype appear in tonsils and blood - Liang, Chunguang; Spörl, Silvia; Xiao, Yin; Habenicht, Katharina M.; Haeusl, Sigrun S.; Sandner, Isabel; Winkler, Julia; Strieder, Nicholas; Eder, Rüdiger; Stanewsky, Hanna; Alexiou, Christoph; Dudziak, Diana; et al. (Communications Biology, 2024)
Most subsets of CD4+ T-follicular helper cells occur in blood and tonsils, but location enforces specific gene expression. One subtype reveals a cytotoxic phenotype, is circulating or extrafollicular, oligoclonal and shares TCRs with other clusters.
CRIS-Team Scopus Importer:2024-07-26

Pharmacodynamic Effect of mTOR Inhibition-based Immunosuppressive Therapy on T- and B-cell Subsets After Renal Transplantation - Wei, Xinyi; Weber, Sabine; Yin, Decheng; Allabauer, Ida; Jobst-Schwan, Tilman; Wiesener, Michael; Schiffer, Mario; Dudziak, Diana; Lehmann, Christian; Wölfle, Joachim; Hörning, André (Transplantation Direct, 2024)
Background. The mammalian target of rapamycin inhibitor (mTORi) therapy after kidney transplantation is solely monitored pharmacokinetically, not necessarily reflecting PI3K-Akt-mTOR pathway blockade efficacy leading to potential under- or overimmunosuppression. Methods. In this cross-sectional study, phosphoflow cytometry was used to determine the efficacy of mTOR inhibition in peripheral T- and B-lymphocyte subsets by assessing p70S6 kinase (p70S6K) phosphorylation in renal transplant recipients upon treatment with a combination of either mTORi and calcineurin inhibitors (n = 18), or mTORi with mycophenolic acid (n = 9). Nine dialysis patients with end-stage renal disease and 17 healthy age-matched volunteers served as controls. Results. mTORi treatment reduced p70S6K phosphorylation in CD4+, CD8+ T, and CD19+ B cells compared with healthy controls (HCs). Subpopulation analysis of CD4+ T cells and CD19+ B cells revealed a significant reduction of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells (P < 0.05), CD24hiCD38hi transitional B cells (P < 0.001), CD24+CD38− memory B cells (P < 0.001), and CD24intCD38int-naive B cells (P < 0.05) upon mTORi treatment, whereas CD4+CD45RA−CD25++CD127− regulatory T cells and CD24−CD38hi plasmablasts were not affected. Compared with mTORi + mycophenolic acid therapy, mTORi + calcineurin inhibitor treatment exhibited an even stronger inhibition of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells and CD8+ T cells. However, trough levels of mTORi did not correlate with p70S6K phosphorylation. Conclusions. mTORi selectively inhibited p70S6K phosphorylation in select lymphocyte subtypes. Assessing p70S6K phosphorylation by phosphoflow cytometry may serve as an approach to understand cell subset specific effects of mTORi providing detailed pharmacodynamic information for individualizing immunosuppression.
CRIS-Team Scopus Importer:2024-07-19

Phosphatase PTPN22 Regulates Dendritic Cell Homeostasis and cDC2 Dependent T Cell Responses - Purvis, Harriet A.; Clarke, Fiona; Montgomery, Anna B.; Colas, Chloe; Bibby, Jack A.; Cornish, Georgina H.; Dai, Xuezhi; Dudziak, Diana; Rawlings, David J.; Zamoyska, Rose; Guermonprez, Pierre; Cope, Andrew P. (Frontiers in Immunology, 2020)
Dendritic cells (DCs) are specialized antigen presenting cells that instruct T cell responses through sensing environmental and inflammatory danger signals. Maintaining the homeostasis of the multiple functionally distinct conventional dendritic cells (cDC) subsets that exist in vivo is crucial for regulating immune responses, with changes in numbers sufficient to break immune tolerance. Using Ptpn22-/- mice we demonstrate that the phosphatase PTPN22 is a highly selective, negative regulator of cDC2 homeostasis, preventing excessive population expansion from as early as 3 weeks of age. Mechanistically, PTPN22 mediates cDC2 homeostasis in a cell intrinsic manner by restricting cDC2 proliferation. A single nucleotide polymorphism, PTPN22R620W, is one of the strongest genetic risk factors for multiple autoantibody associated human autoimmune diseases. We demonstrate that cDC2 are also expanded in mice carrying the orthologous PTPN22619W mutation. As a consequence, cDC2 dependent CD4+ T cell proliferation and T follicular helper cell responses are increased. Collectively, our data demonstrate that PTPN22 controls cDC2 homeostasis, which in turn ensures appropriate cDC2-dependent T cell responses under antigenic challenge. Our findings provide a link between perturbations in DC development and susceptibility to a broad spectrum of PTPN22R620W associated human autoimmune diseases.
CRIS-Team Scopus Importer:2020-03-31
Keywords: autoimmunity; cDC2; dendritic cell; homeostasis; polymorphism; proliferation; PTPN22; T follicular helper cell

Protocol for mapping the heterogeneous dendritic cell network across the murine tissue landscape via high-dimensional flow cytometry - Amon, Lukas; Seichter, Anna; Vurnek, Damir; Tchitashvili, Giorgi; Heß, Isabel; Heger, Lukas; Lehmann, Christian; Dudziak, Diana (STAR Protocols, 2024)
Dendritic cells (DCs) populate nearly all tissues and represent the central orchestrators of immunity. Here, we present a protocol for the mild but efficient preparation of single-cell suspensions from multiple murine tissues and the downstream analysis of the DC network via high-parameter flow cytometry. Additionally, we provide evaluation strategies that facilitate the stringent separation of the DC family from other myeloid cells, particularly macrophages and monocytes, and include an in-depth assessment of DC-intrinsic heterogeneity. For complete details on the use and execution of this protocol, please refer to Amon et al.1
CRIS-Team Scopus Importer:2024-07-19
Keywords: Cell Biology; Cell isolation; Flow Cytometry; Immunology; Single Cell

Regulation of autoantibody activity by the IL-23-TH17 axis determines the onset of autoimmune disease. - Pfeifle, René; Rothe, Tobias; Ipseiz, Natacha; Scherer, Hans U.; Culemann, Stephan; Harre, Ulrike; Ackermann, Jochen; Seefried, Martina; Kleyer, Arnd; Uderhardt, Stefan; Haugg, Benjamin; Huebert, Axel J.; et al. (Nature Immunology, 2017)
The checkpoints and mechanisms that contribute to autoantibody-driven disease are as yet incompletely understood. Here we identified the axis of interleukin 23 (IL-23) and the TH17 subset of helper T cells as a decisive factor that controlled the intrinsic inflammatory activity of autoantibodies and triggered the clinical onset of autoimmune arthritis. By instructing B cells in an IL-22- and IL-21-dependent manner, TH17 cells regulated the expression of β-galactoside α2,6-sialyltransferase 1 in newly differentiating antibody-producing cells and determined the glycosylation profile and activity of immunoglobulin G (IgG) produced by the plasma cells that subsequently emerged. Asymptomatic humans with rheumatoid arthritis (RA)-specific autoantibodies showed identical changes in the activity and glycosylation of autoreactive IgG antibodies before shifting to the inflammatory phase of RA; thus, our results identify an IL-23-TH17 cell-dependent pathway that controls autoantibody activity and unmasks a preexisting breach in immunotoleranc

Select Clr-g Expression on Activated Dendritic Cells Facilitates Cognate Interaction with a Minor Subset of Splenic NK Cells Expressing the Inhibitory Nkrp1g Receptor - Friede, Miriam E.; Leibelt, Stefan; Dudziak, Diana; Steinle, Alexander (Journal of Immunology, 2018)
Natural killer gene complex-encoded immunomodulatory C-type lectin-like receptors include members of the NKRP1 and C-type lectin-like 2 (CLEC2) gene families, which constitute genetically linked receptor-ligand pairs and are thought to allow for NK cell-mediated immunosurveillance of stressed or infected tissues. The mouse C-type lectin-like receptor Nkrp1g was previously shown to form several receptor-ligand pairs with the CLEC2 proteins Clr-d, Clr-f, and Clr-g, respectively. However, the physiological expression of Nkrp1g and its CLEC2 ligands as well as their functional relevance remained poorly understood. Recently, we demonstrated a gut-restricted expression of Clr-f on intestinal epithelial cells that is spatially matched by Nkrp1g on subsets of intraepithelial lymphocytes. In this study, we investigated expression and ligand interaction of Nkrp1g in the splenic compartment, and found an exclusive expression on a small subset of NK cells that upregulates Nkrp1g after cytokine exposure. Whereas transcripts of Clr-d and Clr-f are virtually absent from the spleen, Clr-g transcripts were abundantly detected throughout different leukocyte populations and hematopoietic cell lines. However, a newly generated anti-Clr-g mAb detected only residual Clr-g surface expression on splenic monocytes, whereas many hematopoietic cell lines brightly display Clr-g. Clr-g surface expression was strongly upregulated on splenic CD8α+ conventional dendritic cells (DCs) and plasmacytoid DCs upon TLR-mediated activation and detectable by Nkrp1g, which dampens NK cell effector functions upon Clr-g engagement. Hence, different to the intestinal tract, in the spleen, Nkrp1g is selectively expressed by a subset of NK cells, thereby potentially allowing for an inhibitory engagement with Clr-g-expressing activated DCs during immune responses.
EVALuna2:34802

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, Chunguang; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, Olaf; Nimmerjahn, Falk; Burmazovic, Ivana Ivanovic; Kunz, Meik; et al. (Science Signaling, 2021)
The detection of microorganisms and danger signals by pattern recognition receptors on dendritic cells (DCs) and the consequent formation of inflammasomes are pivotal for initiating protective immune responses. Although the activation of inflammasomes leading to secretion of the cytokine IL-1 is typically accompanied by pyroptosis (an inflammatory form of lytic programmed cell death), some cells can survive and exist in a state of hyperactivation. Here, we found that the conventional type 2 DC (cDC2) subset is the major human DC subset that is transcriptionally and functionally poised for inflammasome formation and response without pyroptosis. When cDC2 were stimulated with ligands that relatively weakly activated the inflammasome, the cells did not enter pyroptosis but instead secreted IL-12 family cytokines and IL-1. These cytokines induced prominent T helper type 1 (TH1) and TH17 responses that were superior to those seen in response to Toll-like receptor (TLR) stimulation alone or to stronger, classical inflammasome ligands. These findings not only define the human cDC2 subpopulation as a prime target for the treatment of inflammasome-dependent inflammatory diseases but may also inform new approaches for adjuvant and vaccine development.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Dendritic cells; cDC2; CD1c; inflammasome; hyperactivation; L18-MDP; T cell differentiation

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Heger, Lukas; Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, C.; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, O.; Nimmerjahn, Falk; Ivanovic-Burmazovic, I.; et al. (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Semi-Automatic Cell Correspondence Analysis Using Iterative Point Cloud Registration - Chen, Shuqing; Gehrer, Simone; Kaliman, Sara; Ravikumar, Nishant; Becit, Abdurrahman; Aliee, Maryam; Dudziak, Diana; Merkel, Rudolf; Smith, Ana-Suncana; Maier, Andreas (Bildverarbeitung für die Medizin 2019. Informatik aktuell., 2019)

Siglec-H-Deficient Mice Show Enhanced Type I IFN Responses, but Do Not Develop Autoimmunity After Influenza or LCMV Infections - Szumilas, Nadine; Corneth, Odilia B.J.; Lehmann, Christian; Schmitt, Heike; Cunz, Svenia; Cullen, Jolie G.; Chu, Talyn; Marosán, Anita; Mócsai, Attila; Benes, Vladimir; Zehn, Dietmar; Dudziak, Diana; et al. (Frontiers in Immunology, 2021)
Siglec-H is a DAP12-associated receptor on plasmacytoid dendritic cells (pDCs) and microglia. Siglec-H inhibits TLR9-induced IFN-α production by pDCs. Previously, it was found that Siglec-H-deficient mice develop a lupus-like severe autoimmune disease after persistent murine cytomegalovirus (mCMV) infection. This was due to enhanced type I interferon responses, including IFN-α. Here we examined, whether other virus infections can also induce autoimmunity in Siglec-H-deficient mice. To this end we infected Siglec-H-deficient mice with influenza virus or with Lymphocytic Choriomeningitis virus (LCMV) clone 13. With both types of viruses we did not observe induction of autoimmune disease in Siglec-H-deficient mice. This can be explained by the fact that both types of viruses are ssRNA viruses that engage TLR7, rather than TLR9. Also, Influenza causes an acute infection that is rapidly cleared and the chronicity of LCMV clone 13 may not be sufficient and may rather suppress pDC functions. Siglec-H inhibited exclusively TLR-9 driven type I interferon responses, but did not affect type II or type III interferon production by pDCs. Siglec-H-deficient pDCs showed impaired Hck expression, which is a Src-family kinase expressed in myeloid cells, and downmodulation of the chemokine receptor CCR9, that has important functions for pDCs. Accordingly, Siglec-H-deficient pDCs showed impaired migration towards the CCR9 ligand CCL25. Furthermore, autoimmune-related genes such as Klk1 and DNase1l3 are downregulated in Siglec-H-deficient pDCs as well. From these findings we conclude that Siglec-H controls TLR-9-dependent, but not TLR-7 dependent inflammatory responses after virus infections and regulates chemokine responsiveness of pDCs.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Interferon-alpha; plasmacytoid dendritic cells; Siglec; SLE; TLR9

Six-Color Confocal Immunofluorescence Microscopy with 4-Laser Lines - Heger, Lukas; Lühr, Jennifer J.; Amon, Lukas; Smith, Ana-Suncana; Eissing, Nathalie; Dudziak, Diana (Methods in Molecular Biology, 2021)
Confocal immunofluorescence microscopy is an advanced imaging technique routinely applied in the laboratory and clinics. Histological analyses are performed from tissue material. In general, a single fluorochrome per laser is employed, limiting simultaneous analysis to four antigens in one staining with a conventional 4-laser line microscope. Here, we describe a protocol for combining fluorochromes with the same excitation but different emission properties that allows for the analysis of six different antigens in confocal immunofluorescence microscopy with a conventional 4-laser line microscope. The proposed multiplexed method permits the identification and characterization of complex cell populations in rare tissue material.
CRIS-Team Scopus Importer:2021-10-01
Keywords: DC; Dendritic cells; Fluorochrome; Histology; Multicolor imaging; Tissue

Spatial, structural and density determinants of DC:T cell interaction under immunostimulatory conditions - Vurnek, D.; Amon, Lukas; Buttazzo, L.; Lehmann, C.; Zaburdaev, Vasily; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Specific phenotype and function of CD56-expressing innate immune cell subsets in human thymus - Gerstner, Stephanie; Köhler, Wolfgang; Heidkamp, Gordon Frederik; Purbojo, Ariawan; Uchida, Shizuka; Ekici, Arif Bülent; Heger, Lukas; Luetke-Eversloh, Merlin; Schubert, Ralf; Bader, Peter; Klingebiel, Thomas; Koehl, Ulrike; et al. (Journal of Leukocyte Biology, 2016)
Whereas innate immune cells, such as NK and innate lymphoid cells (ILCs), have been characterized in different human tissues, knowledge on the thymic CD56-expressing cell subsets is limited. In this study, the rare subpopulations of thymic CD56(+)CD3(-) cells from samples of >100 patients have been successfully analyzed. The results revealed fundamental differences between thymic and peripheral blood (PB) CD56(+)CD3(-) cells. Thymic tissues lacked immunoregulatory CD56(high)CD16(dim) NK cells but showed two Eomes(+)CD56(dim) subsets on which common NK cell markers were significantly altered. CD56(dim)CD16(high) cells expressed high amounts of NKG2A, NKG2D, and CD27 with low CD57. Conversely, CD56(dim)CD16(dim) cells displayed high CD127 but low expression of KIR, NKG2D, and natural cytotoxicity receptors (NCRs). Thymic CD56(+)CD3(-) cells were able to gain cytotoxicity but were especially immunoregulatory cells, producing a broad range of cytokines. Finally, one population of thymic CD56(+) cells resembled conventional NK cells, whereas the other represented a novel, noncanonical NK subset.
EVALuna2:9311

Subsets of CD1c+ DCs: Dendritic Cell Versus Monocyte Lineage - Heger, Lukas; Hofer, Thomas P.; Bigley, Venetia; de Vries, I. Jolanda M.; Dalod, Marc; Dudziak, Diana; Ziegler-Heitbrock, Loems (Frontiers in Immunology, 2020)
Currently three bona fide dendritic cell (DC) types are distinguished in human blood. Herein we focus on type 2 DCs (DC2s) and compare the three defining markers CD1c, CD172, and CD301. When using CD1c to define DC2s, a CD14+ and a CD14− subset can be detected. The CD14+ subset shares features with monocytes, and this includes substantially higher expression levels for CD64, CD115, CD163, and S100A8/9. We review the current knowledge of these CD1c+CD14+ cells as compared to the CD1c+CD14− cells with respect to phenotype, function, transcriptomics, and ontogeny. Here, we discuss informative mutations, which suggest that two populations have different developmental requirements. In addition, we cover subsets of CD11c+CD8− DC2s in the mouse, where CLEC12A+ESAMlow cells, as compared to the CLEC12A−ESAMhigh subset, also express higher levels of monocyte-associated markers CD14, CD3, and CD115. Finally, we summarize, for both man and mouse, the data on lower antigen presentation and higher cytokine production in the monocyte-marker expressing DC2 subset, which demonstrate that the DC2 subsets are also functionally distinct.
CRIS-Team Scopus Importer:2020-10-30
Keywords: CD14; CD172; CD1c; CD301; DC subsets; DC2; dendritic cells

Sweet SIGNs: IgG glycosylation leads the way in IVIG-mediated resolution of inflammation - Brückner, Christin; Lehmann, Christian; Dudziak, Diana; Nimmerjahn, Falk (International Immunology, 2017)
A hallmark of many chronic inflammatory and autoimmune diseases is that there is an impaired resolution of inflammation and return to the steady state. The infusion of high doses of pooled serum IgG preparations from thousands of donors [intravenous immunoglobulin (IVIG) therapy] has been shown to induce resolution of inflammation in a variety of chronic inflammatory and autoimmune diseases, suggesting that IgG molecules can instruct the immune system to stop inflammatory processes and initiate the return to the steady state. The aim of this review is to discuss how insights into the mechanism of IVIG activity may help to understand the molecular and cellular pathways underlying resolution of inflammation. We will put a special emphasis on pathways dependent on the IgG FC domain and IgG sialylation, as several recent studies have provided new insights into how this glycosylation-dependent pathway modulates innate and adaptive immune responses through different sets of C-type or I-type lectins.
EVALuna2:34371

Systems Immunology Approaches for Understanding of Primary Dendritic Cell Subpopulations in the Past, Present and Future - Heger, Lukas; Amon, Lukas; Lehmann, Christian; Dudziak, Diana (Elsevier, 2020)
Since their discovery in the 1970s, Dendritic cells (DCs) emerged as central regulators of immune responses controlling the induction and type of T cell immunity. There, DCs orchestrate the delicate balance of inducing protective immune responses against pathogens and tumors, while maintaining tolerance to self. Owing to their low abundance, short life, sensitivity and diversity, researchers had a hard time to dissect and identify specialized DC subsets in mice and men, track their ontogenetic origin and characterize key phenotypic and functional features utilizable for future therapeutic approaches. Thus, the DC community had to empower every technical innovation over the last decades as soon as possible. These advances range from the development of isolation and enrichment protocols to the generation of DC specific antibodies, early subtraction cDNA library screenings, bulk RNA sequencing and microarrays, simple flow cytometry and cell sorting to multicolor flow- and mass cytometry and unbiased -omics studies including analysis of the epigenome, transcriptome, lipidome and proteome. Within this review, we aim to briefly summarize the history of dendritic cell research ranging from their discovery to the onset of cutting-edge techniques with focus on unbiased single cell based approaches currently revolutionizing our understanding of DC biology.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Affymetrix array; Agilent array; cDC1; cDC2; Conventional; Genearray; Genespring; Human; Illumina; Microarray; Ontogeny; pDC; Progeny; RNA-seq; scRNAseq; SPADE; Subtraction library; Transcription factor; tSNE; UMAP

Th17 Cell-Mediated Colitis Is Positively Regulated by Interferon Regulatory Factor 4 in a T Cell-Extrinsic Manner - Buchele, Vera; Konein, Patrick; Vogler, Tina; Kunert, Timo; Enderle, Karin; Khan, Hanif; Büttner-Herold, Maike; Lehmann, Christian; Amon, Lukas; Wirtz, Stefan; Dudziak, Diana; Neurath, Markus; et al. (Frontiers in Immunology, 2021)
Inflammatory bowel diseases (IBDs) are characterized by chronic, inflammatory gastrointestinal lesions and often require life-long treatment with immunosuppressants and repetitive surgical interventions. Despite progress in respect to the characterization of molecular mechanisms e.g. exerted by TNF-alpha, currently clinically approved therapeutics fail to provide long-term disease control for most patients. The transcription factor interferon regulatory factor 4 (IRF4) has been shown to play important developmental as well as functional roles within multiple immune cells. In the context of colitis, a T cell-intrinsic role of IRF4 in driving immune-mediated gut pathology is established. Here, we conversely addressed the impact of IRF4 inactivation in non-T cells on T cell driven colitis in vivo. Employing the CD4+CD25− naïve T cell transfer model, we found that T cells fail to elicit colitis in IRF4-deficient compared to IRF4-proficient Rag1−/− mice. Reduced colitis activity in the absence of IRF4 was accompanied by hampered T cell expansion both within the mesenteric lymph node (MLN) and colonic lamina propria (cLP). Furthermore, the influx of various myeloids, presumably inflammation-promoting cells was abrogated overall leading to a less disrupted intestinal barrier. Mechanistically, gene profiling experiments revealed a Th17 response dominated molecular expression signature in colon tissues of IRF4-proficient, colitic Rag1−/− but not in colitis-protected Rag1−/−Irf4−/− mice. Colitis mitigation in Rag1−/−Irf4−/− T cell recipients resulted in reduced frequencies and absolute numbers of IL-17a-producing T cell subsets in MLN and cLP possibly due to a regulation of conventional dendritic cell subset 2 (cDC2) known to impact Th17 differentiation. Together, extending the T cell-intrinsic role for IRF4 in the context of Th17 cell driven colitis, the provided data demonstrate a Th17-inducing and thereby colitis-promoting role of IRF4 through a T cell-extrinsic mechanism highlighting IRF4 as a putative molecular master switch among transcriptional regulators driving immune-mediated intestinal inflammation through both T cell-intrinsic and T cell-extrinsic mechanisms. Future studies need to further dissect IRF4 controlled pathways within distinct IRF4-expressing myeloid cell types, especially cDC2s, to elucidate the precise mechanisms accounting for hampered Th17 formation and, according to our data, the predominant mechanism of colitis protection in Rag1−/−Irf4−/− T cell receiving mice.
CRIS-Team Scopus Importer:2021-02-26
Keywords: inflammatory bowel disease (IBD); interferon regulatory factor 4 (IRF4); intestinal inflammation; myeloid cells; Th17

The delivery of antigens to dendritic cells is a potent futureoption for anti-tumor therapies - Lehmann, Christian; Heger, Lukas; Neubert, K.; Harzer, Christina; Amon, Lukas; Yamazaki, S.; Heidkamp, Gordon Frederik; Eissing, N.; Krug, A.; Leusen, J.; Ravetch, J.; Nimmerjahn, Falk; et al. (2017)
EVALuna2:34372

The distribution of C-type lectin receptors in the Dendritic cell membrane - Lühr, Jennifer; Eissing, N.; Heidkamp, Gordon Frederik; Lehmann, C. H. K.; Heger, Lukas; Dudziak, Diana (2017)
EVALuna2:34370

The Effect of Hyperthermia and Radiotherapy Sequence on Cancer Cell Death and the Immune Phenotype of Breast Cancer Cells - Sengedorj, Azzaya; Hader, Michael; Heger, Lukas; Frey, Benjamin; Dudziak, Diana; Fietkau, Rainer; Ott, Oliver; Scheidegger, Stephan; Barba, Sergio Mingo; Gaipl, Udo; Rückert, Michael (Cancers, 2022)
Hyperthermia (HT) is an accepted treatment for recurrent breast cancer which locally heats the tumor to 39–44◦C, and it is a very potent sensitizer for radiotherapy (RT) and chemotherapy. However, currently little is known about how HT with a distinct temperature, and particularly, how the sequence of HT and RT changes the immune phenotype of breast cancer cells. Therefore, human MDA-MB-231 and MCF-7 breast cancer cells were treated with HT of different temperatures (39, 41 and 44◦C), alone and in combination with RT (2 × 5 Gy) in different sequences, with either RT or HT first, followed by the other. Tumor cell death forms and the expression of immune checkpoint molecules (ICMs) were analyzed by multicolor flow cytometry. Human monocyte-derived dendritic cells (moDCs) were differentiated and co-cultured with the treated cancer cells. In both cell lines, RT was the main stressor for cell death induction, with apoptosis being the prominent cell death form in MCF-7 cells and both apoptosis and necrosis in MDA-MB-231 cells. Here, the sequence of the combined treatments, either RT or HT, did not have a significant impact on the final outcome. The expression of all of the three examined immune suppressive ICMs, namely PD-L1, PD-L2 and HVEM, was significantly increased on MCF-7 cells 120 h after the treatment of RT with HT of any temperature. Of special interest for MDA-MB-231 cells is that only combinations of RT with HT of both 41 and 44◦C induced a significantly increased expression of PD-L2 at all examined time points (24, 48, 72, and 120 h). Generally, high dynamics of ICM expression can be observed after combined RT and HT treatments. There was no significant difference between the different sequences of treatments (either HT + RT or RT + HT) in case of the upregulation of ICMs. Furthermore, the co-culture of moDCs with tumor cells of any treatment had no impact on the expression of activation markers. We conclude that the sequence of HT and RT does not strongly affect the immune phenotype of breast cancer cells. However, when HT is combined with RT, it results in an increased expression of distinct immune suppressive ICMs that should be considered by including immune checkpoint inhibitors in multimodal tumor treatments with RT and HT. Further, combined RT and HT affects the immune system in the effector phase rather than in the priming phase.
CRIS-Team Scopus Importer:2022-04-29
Keywords: breast cancer; dendritic cell activation; hyperthermia; hyperthermia treatment sequence; immune checkpoint molecules; immune phenotype; radiotherapy

The Influence of MHC Class II on B Cell Defects Induced by Invariant Chain/CD74 N-Terminal Fragments - Schneppenheim, Janna; Loock, Ann-Christine; Huettl, Susann; Schweizer, Michaela; Luellmann-Rauch, Renate; Oberg, Hans-Heinrich; Arnold, Philipp; Lehmann, Christian; Dudziak, Diana; Kabelitz, Dieter; Lucius, Ralph; Lennon-Dumenil, Ana-Maria; et al. (Journal of Immunology, 2017)
The invariant chain (CD74) mediates assembly and targeting of MHC class II (MHCII) complexes. In endosomes, CD74 undergoes sequential degradation by different proteases, including cathepsin S (CatS) and the intramembrane protease signal peptide peptidase-like 2a (SPPL2a). In their absence, CD74 N-terminal fragments (NTFs) accumulate. In SPPL2a-/- B cells, such an NTF impairs endosomal trafficking and BCR signal transduction. In mice, this leads to a loss of splenic B cells beyond the transitional stage 1. To gain insight into CD74 determinants and the role of MHCII, we compared B cells from CatS-/- , SPPL2a-/- , and SPPL2a-MHCII double-deficient mice. We assessed differentiation of B cells in bone marrow and spleen and analyzed their endosomal morphology, BCR expression, and signal transduction. We demonstrate that MHCII is dispensable for the B cell phenotype of SPPL2a-/- mice, further supporting a CD74-intrinsic effect. Despite significant vacuolization of endosomal compartments similar to SPPL2a-/- B cells, CatS-/- traditional stage 1 B cells show unimpaired degradation of endocytic cargo, have intact BCR signaling, and do not exhibit any relevant defects in maturation. This could indicate that CD74 NTF-induced structural changes of endosomes are not directly involved in these processes. We further found that the block of CD74 degradation in CatS-/- B cells is incomplete, so that NTF levels are significantly lower than in SPPL2a-/- B cells. This suggests a dose dependency and threshold for the CD74 NTF-associated impairment of B cell signaling and maturation. In addition, different functional properties of the longer, MHCII-bound CD74 NTF could contribute to the milder phenotype of CatS-/- B cells.
EVALuna2:34373

The involvement of Toll-like receptor 9 in the pathogenesis of erosive autoimmune arthritis - Fischer, Anita; Abdollahi-Roodsaz, Shahla; Boehm, Christina; Niederreiter, Birgit; Meyer, Brigitte; Yau, Anthony C. Y.; Lonnblom, Erik; Joosten, Leo A. B.; Koenders, Marije; Lehmann, Christian; Dudziak, Diana; Krönke, Gerhard; et al. (Journal of Cellular and Molecular Medicine, 2018)
Endogenous nucleic acids and their receptors may be involved in the initiation of systemic autoimmune diseases including rheumatoid arthritis (RA). As the role of the DNA sensing Toll-like receptor (TLR) 9 in RA is unclear, we aimed to investigate its involvement in the pathogenesis of autoimmune arthritis using three different experimental models of RA. The data obtained revealed involvement of TLR9 in the T cell-dependent phase of inflammatory arthritis. In rats with pristane-induced arthritis (PIA), TLR9 inhibition before disease onset reduced arthritis significantly and almost completely abolished bone erosion. Accordingly, serum levels of IL-6, α-1-acid-glycoprotein and rheumatoid factor were reduced. Moreover, in TLR9-/- mice, streptococcal cell wall (SCW)-induced arthritis was reduced in the T cell-dependent phase, whereas T cell-independent serum-transfer arthritis was not affected. Remarkably, while TLR7 expression did not change during in vitro osteoclastogenesis, TLR9 expression was higher in precursor cells than in mature osteoclasts and partial inhibition of osteoclastogenesis was achieved only by the TLR9 antagonist. These results demonstrate a pivotal role for TLR9 in the T cell-dependent phases of inflammatory arthritis and additionally suggest some role during osteoclastogenesis. Hence, endogenous DNA seems to be crucially involved in the pathophysiology of inflammatory autoimmune arthritis.
EVALuna2:34780

The ontogenetic path of human dendritic cells - Amon, Lukas; Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Dudziak, Diana (Molecular Immunology, 2020)
Dendritic cells (DCs) orchestrate adaptive immune responses. In healthy individuals, DCs are drivers and fine-tuners of T cell responses directed against invading pathogens or cancer cells. In parallel, DCs control autoreactive T cells, thereby maintaining T cell tolerance. Under various disease conditions, a disruption of this delicate balance can lead to chronic infections, tumor evasion, or autoimmunity. While great efforts have been made to unravel the origin and development of this powerful cell type in mice, only little is known about the ontogeny of human DCs. Here, we summarize the current understanding of the developmental path of DCs from hematopoietic stem cells to fully functional DCs in their local tissue environment and provide a template for the identification of DCs across various tissues.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Conventional; DC; Human; Ontogeny; Progeny; Transcription factor

TILGen: A Program to Investigate Immune Targets in Breast Cancer Patients - First Results on the Influence of Tumor-Infiltrating Lymphocytes - Würfel, Franziska; Erber, Ramona; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Kremer, Anita; Kranich, Hannah; Mackensen, Andreas; Häberle, Lothar; Hack, Carolin; Rauh, Claudia; et al. (Breast Care, 2018)
Background: Despite advancements in the treatment of primary and metastatic breast cancer, many patients lack a durable response to these treatments. Patients with triplenegative breast cancer (TNBC) and human epidermal growth factor receptor 2(HER2)-positive breast cancer who do not have a pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) have a very poor prognosis. Tumor-infiltrating lymphocytes (TILs) have been identified as a predictive marker for pCR after NACT in TNBC and HER2-positive breast cancer. These patient populations could also be suitable for novel treatment strategies including neoepitope-based therapies. This work analyses the effect of TILs on the pCR in neoadjuvantly treated patients in the TILGen study and presents the procedures aimed at establishing neoepitope-based therapies in this study. Methods: Neoadjuvantly treated HER2positive and TNBC patients were eligible for the presented analysis concerning the association between TILs and pCR. A total of 146 patients could be identified within the TILGen study. TILs were evaluated as percentage of stromal tumor tissue in core biopsies at primary diagnosis. The phenotype 'lymphocyte-predominant breast cancer' (LPBC) was associated with pCR by logistic regression adjusted for estrogen receptor status, progesterone receptor status, HER2 status, age at diagnosis, and grading. Results: LPBC was seen in 24 (16.4%) patients. In this patient group, 66.7% achieved a pCR, while the pCR rate was 32.8% in patients with a low TIL count. The adjusted odds ratio was 6.60 (95% confidence interval 2.02-21.56; p < 0.01). Conclusion: TILs are a strong predictor of pCR in TNBC and HER2-positive breast cancer patients. Implications for the use of this information including the effect on prognosis might help to identify patients most likely to benefit from a neoepitope-based therapy approach. (C) 2018 S. Karger GmbH, Freiburg
EVALuna2:34061
Keywords: Tumor-infiltrating lymphocytes; Response; Neoadjuvant chemotherapy; TILGen study

TNF-Mediated Restriction of Arginase 1 Expression in Myeloid Cells Triggers Type 2 NO Synthase Activity at the Site of Infection - Schleicher, Ulrike; Paduch, Katrin; Debus, Andrea; Obermeyer, Stephanie; Koenig, Till; Kling, Jessica C.; Ribechini, Eliana; Dudziak, Diana; Mougiakakos, Dimitrios; Murray, Peter J.; Ostuni, Renato; Koerner, Heinrich; et al. (Cell Reports, 2016)
Neutralization or deletion of tumor necrosis factor (TNF) causes loss of control of intracellular pathogens in mice and humans, but the underlying mechanisms are incompletely understood. Here, we found that TNF antagonized alternative activation of macrophages and dendritic cells by IL-4. TNF inhibited IL-4-induced arginase 1 (Arg1) expression by decreasing histone acetylation, without affecting STAT6 phosphorylation and nuclear translocation. In Leishmania major-infected C57BL/6 wild-type mice, type 2 nitric oxide (NO) synthase (NOS2) was detected in inflammatory dendritic cells or macrophages, some of which co-expressed Arg1. In TNF-deficient mice, Arg1 was hyperexpressed, causing an impaired production of NO in situ. A similar phenotype was seen in L. major-infected BALB/c mice. Arg1 deletion in hematopoietic cells protected these mice from an otherwise lethal disease, although their disease-mediating T cell response (Th2, Treg) was maintained. Thus, deletion or TNF-mediated restriction of Arg1 unleashes the production of NO by NOS2, which is critical for pathogen control.
EVALuna2:7700

Transcriptional control of dendritic cell development and functions - Amon, Lukas; Lehmann, Christian; Baranska, Anna; Schoen, Janina; Heger, Lukas; Dudziak, Diana (Immunobiology of Dendritic Cells Part B, 2019)
Dendritic cells (DCs) are major regulators of adaptive immunity, as they are not only capable to induce efficient immune responses, but are also crucial to maintain peripheral tolerance and thereby inhibit autoimmune reactions. DCs bridge the innate and the adaptive immune system by presenting peptides of self and foreign antigens as peptide MHC complexes to T cells. These properties render DCs as interesting target cells for immunomodulatory therapies in cancer, but also autoimmune diseases. Several subsets of DCs with special properties and functions have been described. Recent achievements in understanding transcriptional programs on single cell level, together with the generation of new murine models targeting specific DC subsets, advanced our current understanding of DC development and function. Thus, DCs arise from precursor cells in the bone marrow with distinct progenitor cell populations splitting the monocyte populations and macrophage populations from the DC lineage, which upon lineage commitment can be separated into conventional cDC1, cDC2, and plasmacytoid DCs (pDCs). The DC populations harbor intrinsic programs enabling them to react for specific pathogens in dependency on the DC subset, and thereby orchestrate T cell immune responses. Similarities, but also varieties, between human and murine DC subpopulations are challenging, and will require further investigation of human specimens under consideration of the influence of the tissue micromilieu and DC subset localization in the future.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Antigen presentation; BatF3; CDP; Cross-presentation; DC; Dendritic cell; IRF; Lineage commitment; Ontogeny; Progenitor; Transcription factor; Zbtb46

Tumor location determines tissue-specific recruitment of tumor-associated macrophages and antibody-dependent immunotherapy response - Lehmann, Birgit; Biburger, Markus; Brückner, Christin; Ipsen Escobedo, Andrea; Gordan, Sina; Lehmann, Christian; Vöhringer, David; Winkler, Thomas; Schaft, Niels; Dudziak, Diana; Sirbu, Horia; Nimmerjahn, Falk; et al. (Science immunology, 2017)
Despite recent advances in activating immune cells to target tumors, the presence of some immune cells, such as tumor-associated macrophages (TAMs) or tumor-associated neutrophils (TANs), may promote rather than inhibit tumor growth. However, it remains unclear how antibody-dependent tumor immunotherapies, such as cytotoxic or checkpoint control antibodies, affect different TAM or TAN populations, which abundantly express activating Fcγ receptors. In this study, we show that the tissue environment determines which cellular effector pathways are responsible for antibody-dependent tumor immunotherapy. Although TAMs derived from Ly6Chigh monocytes recruited by the CCL2-CCR2 axis were critical for tumor immunotherapy of skin tumors, the destruction of lung tumors was CCL2-independent and required the presence of colony-stimulating factor 2–dependent tissue-resident macrophages. Our findings suggest that TAMs may have a dual role not only in promoting tumor growth in certain tissue environments on the one hand but also in contributing to tumor cell destruction during antibody-mediated immunotherapy on the other hand.
EVALuna2:15237
Keywords: Cancer; Macrophages; Tumor associated macrophages; Antibodies; Tumor therapy; Immunotherapy

Unbiased high-dimensional flow cytometry identified NK and DC immune cell signature in Luminal A-type and triple negative breast cancer - Heger, Lukas; Heidkamp, Gordon Frederik; Amon, Lukas; Nimmerjahn, Falk; Bäuerle, Tobias; Maier, Andreas; Erber, Ramona; Hartmann, Arndt; Hack, Carolin; Rübner, Matthias; Hübner, Hanna; Fasching, Peter; et al. (OncoImmunology, 2024)
Breast cancer is the most common malignancy in women worldwide and a highly heterogeneous disease. Four different subtypes are described that differ in the expression of hormone receptors as well as the growth factor receptor HER2. Treatment modalities and survival rate depend on the subtype of breast cancer. However, it is still not clear which patients benefit from immunotherapeutic approaches such as checkpoint blockade. Thus, we aimed to decipher the immune cell signature of the different breast cancer subtypes based on high-dimensional flow cytometry followed by unbiased approaches. Here, we show that the frequency of NK cells is reduced in Luminal A and B as well as triple negative breast cancer and that the phenotype of residual NK cells is changed toward regulatory CD11b−CD16− NK cells. Further, we found higher frequencies of PD-1+ CD4+ and CD8+ T cells in triple negative breast cancer. Moreover, while Luminal A-type breast cancer was enriched for CD14+ cDC2 (named type 3 DC (DC3)), CD14− cDC2 (named DC2) were more frequent in triple negative breast cancer. In contrast, HER2-enriched breast cancer did not show major alterations in the composition of the immune cell compartment in the tumor microenvironment. These findings suggest that patients with Luminal A- and B-type as well as triple negative breast cancer might benefit from immunotherapeutic approaches targeting NK cells.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Breast cancer; immune cell signature; NK cells; PD-1; tumor microenvironment

XCR1 expression distinguishes human conventional dendritic cell type 1 with full effector functions from their immediate precursors - Heger, Lukas; Hatscher, Lukas; Liang, Chunguang; Lehmann, Christian; Amon, Lukas; Lühr, Jennifer J.; Kaszubowski, Tomasz; Nzirorera, Rayk; Schaft, Niels; Dörrie, Jan; Irrgang, Pascal; Tenbusch, Matthias; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Dendritic cells (DCs) are major regulators of innate and adaptive immune responses. DCs can be classified into plasmacytoid DCs and conventional DCs (cDCs) type 1 and 2. Murine and human cDC1 share the mRNA expression of XCR1. Murine studies indicated a specific role of the XCR1-XCL1 axis in the induction of immune responses. Here, we describe that human cDC1 can be distinguished into XCR1- and XCR1+ cDC1 in lymphoid as well as nonlymphoid tissues. Steady-state XCR1+ cDC1 display a preactivated phenotype compared to XCR1- cDC1. Upon stimulation, XCR1+ cDC1, but not XCR1- cDC1, secreted high levels of inflammatory cytokines as well as chemokines. This was associated with enhanced activation of NK cells mediated by XCR1+ cDC1. Moreover, XCR1+ cDC1 excelled in inhibiting replication of Influenza A virus. Further, under DC differentiation conditions, XCR1- cDC1 developed into XCR1+ cDC1. After acquisition of XCR1 expression, XCR1- cDC1 secreted comparable level of inflammatory cytokines. Thus, XCR1 is a marker of terminally differentiated cDC1 that licenses the antiviral effector functions of human cDC1, while XCR1- cDC1 seem to represent a late immediate precursor of cDC1.
CRIS-Team Scopus Importer:2023-08-25
Keywords: antiviral immunity; cDC1; DC differentiation; IL-12; XCR1